Carbon aerogel-based electrode material and method for making the same

By doping silicon into a carbon aerogel, nanoporous carbon materials with fibrous morphology and optimized pore structure are solved, and the problems of low mechanical strength caused by limited capacity of lithium-ion battery anode material and silicon expansion are achieved, and efficient electrochemical performance and cyclic stability are achieved.

CN113767486BActive Publication Date: 2025-04-15ASPEN AEROGELS INC
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202080030973.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-02-27
Filing Date
2020-02-27
Publication Date
2025-04-15
Estimated Expiration
2040-02-27

AI Technical Summary

Technical Problem

The graphite capacity of the anode material of existing lithium-ion batteries is limited, and silicon, as an alternative material, expands in volume during lithiation, resulting in low mechanical strength and poor electrochemical performance.

Method used

A nanoporous carbon material was developed to form an anode material with a fibrous morphology and an optimized pore structure by doping silicon into a carbon aerogel. The material comprises more than 10% silicon-based material, with at least 20% silicon utilization, and with high conductivity, mechanical strength and suitable pore volume.

Benefits of technology

It has achieved the improvement of the capacity and mechanical strength of the anode material of lithium-ion batteries, solved the structural problems caused by silicon expansion, and improved the electrochemical performance and cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113767486B_ABST
    Figure CN113767486B_ABST
Patent Text Reader

Abstract

Nanoporous carbon-based scaffolds or structures, and in particular carbon aerogels, and their manufacture and use are provided. Embodiments include a silicon-doped anode material for a lithium-ion battery, wherein the anode material comprises polyimide-derived carbon aerogel beads. The carbon aerogel contains silicon particles and accommodates the expansion of the silicon particles during lithiation. The anode material provides optimal properties for use in a lithium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Citation of Related Applications

[0002] This application claims the benefit of priority to U.S. Patent Application Serial No. 16 / 803,348, filed on February 27, 2020, and U.S. Provisional Patent Application No. 62 / 811,230, filed on February 27, 2019, each of which is incorporated herein by reference in its entirety, with any definitions of terms set forth in this application. Technical Field

[0003] The present invention generally relates to nanoporous carbon-based materials and more particularly to carbon aerogels suitable for use in environments containing electrochemical reactions, such as as electrode materials in lithium-ion batteries. Background Art

[0004] Aerogel is a solid material including a highly porous network of micro-sized pores and meso-sized pores. Depending on the precursor material used and the processing performed, when the density of the aerogel is about 0.05 g / cc, the pores of the aerogel generally account for more than 90% of the volume. Aerogels are generally prepared by removing solvent from a gel (a solid network containing its solvent) in a manner that allows the shrinkage caused by the capillary forces at the surface of the gel to be minimal or non-shrinking. Methods for removing solvents include, but are not limited to, supercritical drying (or drying with a supercritical fluid so that the low surface tension of the supercritical fluid is exchanged with a transient solvent in the gel), exchange of solvent with a supercritical fluid, exchange of solvent with a fluid subsequently converted to a supercritical state, subcritical or near-critical drying, and sublimation of frozen solvents during freeze drying, see, for example, PCT Patent Application Publication No. WO2016127084A1. It should be noted that when dried under ambient conditions, gel shrinkage may occur as the solvent evaporates, and a xerogel is formed. Therefore, the preparation of aerogels by sol-gel process or other polymerization processes usually proceeds in a series of steps: dissolution of solute in solvent, formation of sol / solution / mixture, formation of gel (which may involve additional cross-linking), and removal of solvent by supercritical drying technique or any other method to remove solvent from gel without causing pore collapse.

[0005] Aerogels can be formed from inorganic and / or organic materials. When formed from organic materials - for example, such as phenols, resorcinol-formaldehyde (RF), phloroglucinol furfural (PF), polyacrylonitrile (PAN), polyimide (PI), polyurethane (PU), polybutadiene, polydicyclopentadiene and their precursors or polymer derivatives - aerogels can be carbonized (e.g., by pyrolysis) to form carbon aerogels, which may have different or overlapping properties (e.g., pore volume, pore size distribution, morphology, etc.) depending on the precursor materials and methods used. However, in all cases, there are certain deficiencies based on the materials and applications, such as low pore volume, wide pore size distribution, low mechanical strength, etc. Recently, efforts have been made to develop and characterize carbon aerogels as electrode materials with improved performance for application in energy storage devices such as lithium-ion batteries (LIBs).

[0006] LIBs are widely used in applications ranging from handheld electronics to automobiles. They are a type of rechargeable battery in which lithium ions move from the anode to the cathode during discharge and from the cathode to the anode during charge. Typically, the cathode is formed of lithium metal (e.g., cobalt, nickel, manganese) oxide, while the anode is formed of graphite, in which the lithium ions are intercalated into graphite layers during charging (energy storage). Graphite is widely used because it has a higher lithium intercalation rate than other known carbons.

[0007] While the demand for higher capacity anode and cathode materials continues to increase, a major drawback of conventional LIBs is the limited capacity of graphite; in other words, graphite can only hold a limited amount of lithium. It is well known that silicon has a greater affinity for lithium than graphite (carbon) and is able to store larger amounts of lithium than graphite during charging, theoretically resulting in a higher capacity on the anode side of the LIB. In comparison, the theoretical capacity of graphite combined with lithium is 372mAh / g, while the theoretical capacity of silicon is 4200mAh / g. These values ​​make it desirable to arrange as much silicon as possible within the anode. However, a considerable problem with silicon is that its volume expands 3-4 times when fully lithiated (and often breaks or cracks), which greatly limits the amount of silicon that can be placed within the electrode.

[0008] Therefore, there is a need for an improved nanoporous carbon material comprising a functional morphology and an optimal pore structure while solving at least one of the above problems. However, considering the technology considered as a whole when making the present invention, it is not obvious to those skilled in the art how to overcome the shortcomings of the prior art.

[0009] Although certain aspects of conventional technology have been discussed to facilitate the disclosure of the present invention, applicants by no means abandon these technical aspects and believe that the claimed invention may include one or more of the conventional technical aspects discussed herein, especially in combination with the innovative aspects described herein.

[0010] The present invention can solve one or more problems and deficiencies in the art discussed above. However, it is expected that the present invention can prove to be useful for solving other problems and shortcomings in many technical fields. Therefore, the claimed invention is not necessarily to be construed as limited to solving any specific problem or disadvantage discussed herein.

[0011] In this specification, when a document, operation or item is referenced or discussed, such reference or discussion is not an admission that the document, operation or item or any combination thereof was publicly available, known to the public, part of the common general knowledge on the priority date, or otherwise constituted prior art under applicable provisions; or was known to be relevant to any problem attempted to be solved in this specification. Summary of the invention

[0012] A new, useful and non-obvious invention satisfies a long-standing but heretofore unmet need for improved nanoporous carbon materials.

[0013] A first general aspect relates to a carbon composition comprising a carbon material, such as a nanoporous carbon material, and a silicon-based material. The carbon material comprises a pore structure, and the carbon composition comprises greater than about 10 wt. % of the silicon-based material and has a silicon utilization of at least about 20%.

[0014] In exemplary embodiments, the carbon material has one or more pore structures comprising a fibrous morphology, a Young's modulus of at least about 0.2 GPa, an electrical conductivity of at least about 10 S / cm, and a density of about 0.15 g / cc to about 1.5 g / cc.

[0015] In another exemplary embodiment, the carbon composition includes a silicon-doped nanoporous carbon material having a silicon utilization of at least about 20%, wherein the carbon material is doped with greater than about 25% silicon by weight of the carbon material. Optionally, the carbon material may have an electrical conductivity of at least about 10 S / cm. Optionally, the carbon material may have a Young's modulus of at least about 0.2 GPa.

[0016] In a further exemplary embodiment, the carbon composition includes a silicon-doped nanoporous carbon material having the following properties: a pore structure comprising a fibrous morphology, a Young's modulus of at least about 0.2 GPa, a density of about 0.15 g / cc to about 1.5 g / cc, and a silicon utilization of at least about 20%. Optionally, the carbon material may have a conductivity of at least about 10 S / cm.

[0017] In another exemplary embodiment, the carbon composition includes a silicon-doped nanoporous carbon material having the following properties: a pore structure comprising a fibrous morphology, a conductivity of at least 10 S / cm, a density of about 0.15 g / cc to about 1.5 g / cc, and a silicon utilization of at least about 20%. Optionally, the carbon material may have a Young's modulus of at least about 0.2 GPa.

[0018] In any embodiment, the nanoporous carbon material can be a carbon aerogel, such as an imide-derived carbon aerogel, such as a polyimide-derived carbon aerogel. In further embodiments, the carbon aerogel can be in a monolithic or granular form, such as a powder. When the carbon aerogel is present in the form of a monolithic structure, the carbon material can be substantially free of a binder or completely free of a binder. Alternatively or additionally, the thickness of the monolithic carbon aerogel can be from about 10 microns to about 500 microns.

[0019] In exemplary embodiments where the carbon aerogel is in particulate form, the particulate carbon aerogel may have a diameter of about 1 micrometer to about 50 micrometers.

[0020] In any embodiment, the pore structure of the nanoporous carbon material can be characterized in that the pores of the carbon material partially, substantially or completely surround the silicon-based material, such as by forming an interconnected structure around the silicon characterized by multiple connection points between the silicon and the pore walls. For example, the silicon-based material can be at least partially present within the pore structure of the carbon material.

[0021] In any embodiment, the nanoporous carbon material may be doped with about 5% to 80% silicon by weight of the carbon material. For example, the carbon material may include about 25% to about 65% silicon by weight of the carbon material.

[0022] In any embodiment, the nanoporous carbon material may have a pore volume of at least 0.3 cc / g.

[0023] In any embodiment, the nanoporous carbon material may have a pre-lithiation porosity of about 10% to about 80%.

[0024] In any embodiment, the carbon material (eg, nanoporous carbon material) may include at least about 4 wt % residual nitrogen.

[0025] In any embodiment, the silicon-doped nanoporous carbon material may have a capacity of at least about 800 mAh / g. For example, the silicon-doped nanoporous carbon material may have a capacity of up to about 2000 mAh / g.

[0026] In any embodiment, the pore structure of the nanoporous carbon material may include a full width at half maximum of about 50 nm or less (ie, a narrow pore size distribution).

[0027] In any embodiment, the pore structure of the nanoporous carbon material may include a pore size at a maximum peak from the distribution of about 100 nm or less.

[0028] In any embodiment, the fibrous morphology of the nanoporous carbon material may include an average pillar width of about 2-10 nm, or, even more specifically, about 2-5 nm.

[0029] Exemplary embodiments provide a collector-free, binder-free, interconnected anode material for lithium-ion batteries. The anode material includes an open-pore, monolithic, polyimide-derived nanoporous carbon material (also referred to as a CPI composite) having an array of fibrous networks and pores, wherein silicon particles are located in the pores surrounded by the fibrous network, which account for about 20% to 80% of the weight of the anode material. The fibrous network includes an average pillar width of about 2-10 nm. The carbon material has a porosity of about 20% to about 50%, wherein the pores include pores containing silicon particles in an unlithiated state and can accommodate lithium, volume-expanded silicon particles. The carbon aerogel has the following characteristics: a pore volume of about 0.1 cc / g or more, a substantially uniform pore size distribution, a half-height full width of about 50 nm or less, and a pore size of 100 nm or less at the maximum peak of the distribution. The resulting anode material has the following properties: density of about 0.50 g / cc to about 1.5 g / cc, conductivity of about 10 S / cm or more, Young's modulus of about 0.5 GPa or more, and thickness of about 10 microns to about 200 microns.

[0030] Exemplary embodiments provide a collector-free, binder-free anode material for a lithium-based energy storage device. The anode material comprises an open-pore, monolithic nanoporous carbon material having a fibrous network and an array of pores, wherein silicon particles are located in pores surrounded by the fibrous network, which accounts for more than 0% and less than about 95% of the weight of the anode material. The fibrous network includes an average strut width of about 2-10 nm, which acts as a carbon coating for silicon particles and can protect silicon particles from breaking during lithiation. The carbon material has a porosity of about 80% or less, wherein the pores include pores surrounding silicon particles in an unlithiated state and can accommodate silicon particles in a lithiated, volume-expanded state. The carbon aerogel has the following characteristics: a pore volume of about 0.3 cc / g or greater, a substantially uniform pore size distribution, a half-height full width of about 50 nm or less, and a pore size of about 100 nm or less from the maximum peak of the distribution. The resulting anode material has the following properties: density of about 0.50 g / cc to about 1.5 g / cc, conductivity of about 10 S / cm or greater, Young's modulus of about 0.5 GPa or greater, and thickness of about 10 microns to about 4 cm.

[0031] Other embodiments are directed to a binder-free composite material comprising an open-cell, porous carbon support having an array of pores and an electrochemically active material disposed within the array of pores of the carbon support and in direct contact with the carbon support, such that the carbon support has a porosity of about 90% or less. The electrochemically active material comprises about 5% to 65% of the weight of the composite material. The carbon aerogel has the following characteristics: a pore volume of about 0.3 cc / g or greater, and a substantially uniform pore size distribution with a full width at half maximum of about 50 nm or less.

[0032] Other embodiments relate to a composite material comprising an open-pore, nanoporous carbon network and an electrochemically active material disposed within the nanoporous carbon network. The carbon network has a porosity of about 90% or less and a substantially uniform pore size distribution with a full width at half maximum of about 50 nm or less. The composite material is formed as a monolith or a powder. Optionally, the material has a conductivity of about 10 S / cm or more. Optionally, the material has a Young's modulus of about 0.5 GPa or more and a thickness of 10 microns to about 500 microns.

[0033] Another embodiment provides a monolithic polyimide derived carbon aerogel composite containing silicon formed from a nanoporous carbon material, wherein the composite is binder-free and wherein silicon particles are embedded in the monolithic polyimide derived carbon aerogel composite.

[0034] Optionally, the composite material may be pre-doped with a metal or metal oxide selected from the group consisting of tin, sulfur, phosphorus, nickel, copper, cobalt, manganese, lithium, magnesium, iron, zinc, boron, titanium, aluminum oxide, titanium oxide, niobium oxide, molybdenum oxide, silicon dioxide and aluminosilicates.

[0035] Optionally, the silicon particles may be pre-doped with a p-type acceptor selected from the group consisting of boron, aluminum, gallium and indium. Alternatively, the silicon particles may be pre-doped with an n-type donor selected from the group consisting of phosphorus, lithium, arsenic, antimony and bismuth.

[0036] Optionally, the carbon aerogel comprises a fibrous morphology comprising an average strut width of about 2-10 nm.

[0037] A further embodiment provides an electrode comprising the described nanoporous carbon material. The electrode may be an anode and optionally does not contain a different current collector. Another embodiment provides an electrochemical cell comprising the described carbon composition, nanoporous carbon material and / or electrode. A further embodiment provides an energy storage device, such as a battery or more specifically a lithium ion battery, comprising the described carbon composition, nanoporous carbon material and / or electrochemical cell.

[0038] Further general aspects relate to methods of forming or making carbon compositions. In an exemplary embodiment, a method includes providing a mixture of a polyimide precursor and a silicon-based material, chemically or thermally imidizing the mixture, such as by adding an imidization catalyst or by heating; drying the imidized mixture to produce a porous polyimide silicon composite material; and carbonizing (e.g., pyrolyzing) the porous polyimide silicon composite material to produce a carbon composition having greater than about 25% by weight silicon and a porosity of about 10% to about 90%. In some embodiments, the method further includes combining the mixture with a medium (e.g., a dispersion medium) that is immiscible with the mixture to form droplets of the imidized mixture. For example, an emulsion can be formed with the imidized mixture as the dispersed phase. In an exemplary embodiment, the method also includes drying the droplets to form particles. In any embodiment, the carbon composition may include a carbon aerogel and may be formed as a whole or particles.

[0039] In an exemplary embodiment, the method includes forming or manufacturing a continuous porous carbon silicon composite material, such as a carbon aerogel. An imide precursor, such as a diamine and a dianhydride, each of which may contain an aromatic group and / or an aliphatic group, is mixed in a suitable solvent (e.g., a polar aprotic solvent). Before adding an imidization catalyst, an additive, such as silicon particles in this embodiment, is mixed into the imide precursor in the solvent. An imidization catalyst is then added to initiate imidization. In an alternative embodiment, imidization can be performed by thermal imidization. A gel is formed in which additive particles, such as silicon particles, are uniformly dispersed. The resulting mixture is then dried to produce a continuous porous polyimide silicon composite material, wherein subcritical and / or supercritical carbon dioxide can be used for drying. Optionally, the polyimide silicon composite material can be densified. For example, the polyimide silicon composite material can be compressed, preferably uniaxially compressed (e.g., up to 95% strain), to increase the density, which can be adjusted to up to about 1.5 g / cc based on the amount of compression. Whether or not compressed, the polyimide silicon composite is pyrolyzed to obtain a continuous porous carbon silicon composite, wherein the resulting composite comprises greater than 0 wt % and less than about 95 wt % silicon, and comprises a porosity of about 5%-99%. In certain embodiments, the pyrolysis may be performed at a maximum temperature of about 750° C. to about 1600° C., optionally with graphitization at about 1600° C. to as high as about 3000° C.

[0040] Another embodiment provides a method for forming or manufacturing a continuous porous carbon silicon composite material (e.g., carbon aerogel). A polyimide precursor, such as a diamine and a dianhydride, each of which may include an aromatic group and / or an aliphatic group, is mixed in a suitable solvent (e.g., a polar aprotic solvent). Before adding an imidization catalyst, a silicate (e.g., silicon dioxide, aluminosilicate, and / or halloysite) and a reducing agent (e.g., magnesium, lithium, sodium, potassium, aluminum, calcium, or a combination thereof) are mixed into the polyimide precursor in the solvent. The imidization catalyst is then added. In an alternative embodiment, imidization can be performed by thermal imidization. The resulting mixture is then dried to produce a continuous porous polyimide silicate and reducing agent composite material, wherein the drying can be performed using subcritical and / or supercritical carbon dioxide. Optionally, the polyimide silicate and reducing agent composite material can be compressed, preferably uniaxially compressed (e.g., up to 95% strain), to increase the density, which can be adjusted to up to about 1.5 g / cc based on the amount of compression. Whether or not compression is performed, the polyimide silicate and reducing agent composite material is heated under pyrolysis and reducing ambient conditions to produce a continuous porous carbon-silicon composite material, wherein the resulting composite material comprises greater than 0 wt % and less than about 95 wt % silicon and comprises a porosity of about 5%-99%. In certain embodiments, pyrolysis can be performed at a maximum temperature of about 750° C. to about 1600° C., optionally with graphitization at about 1600° C. to as high as about 3000° C. In addition, the silicate and reducing agent can be reacted with hydrogen under inert conditions at a temperature above about 700° C. to form silicon in situ in the carbon composite material.

[0041] A further embodiment provides a method for forming or manufacturing a porous carbon silicon composite material (such as a silicon-doped carbon aerogel). A polyimide precursor, such as a diamine and a dianhydride, each of which may include an aromatic group and / or an aliphatic group, is mixed in a suitable solvent (e.g., a polar aprotic solvent). An imidization catalyst is then added. In an alternative embodiment, imidization can be completed by thermal imidization. The resulting mixture is then dried to produce a continuous porous polyimide, wherein the drying can be performed under subcritical conditions and / or using supercritical carbon dioxide.

[0042] Optionally, the polyimide can be compressed, preferably uniaxially compressed (e.g., up to 95% strain), to increase density, adjustable up to about 1.5 g / cc based on the amount of compression. Whether or not compression is performed, the polyimide can be pyrolyzed to produce a continuous porous carbon. Silicon is then deposited on or in the silicon to produce a continuous porous silicon composite material containing greater than 0% and less than about 95% silicon by weight and including a porosity of about 5%-99%. In certain embodiments, pyrolysis can be performed at a maximum temperature of about 750°C to about 1600°C, optionally graphitized at about 1600°C to about 3000°C.

[0043] Optionally, silicon can be deposited by dipping the porous carbon into a silane precursor that forms silicon, and then heating under inert conditions to decompose the silane to form a conformal silicon coating in the porous carbon. This dipping process can be performed multiple times to increase thickness and silicon content (by weight) up to about 95%. In other embodiments, silicon can be deposited by atomic layer deposition or chemical vapor deposition (CVD).

[0044] In any of the above methods for producing a carbon composition (e.g., a continuous porous carbon-silicon composite), the carbon composition may optionally be a monolithic or independent structure, may be prepared on or off a substrate, may be formed into beads, or may be micronized into a powder form. In addition, the composite may or may not be reinforced with a nonwoven or woven material (e.g., fiber, foam, etc.).

[0045] These and other important objects, advantages and features of the present invention will become clear as the disclosure proceeds.

[0046] The present invention accordingly comprises the features of construction, combination of elements and arrangement of parts which will be exemplified in the disclosure set forth hereinafter and the scope of the invention will be indicated in the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] For a full and clear understanding of the present invention, reference should be made to the following detailed description taken in conjunction with the accompanying drawings, in which:

[0048] Figure 1 is a flow chart illustrating the formation of carbon aerogels for use in battery applications.

[0049] Figure 2 The discharge capacity over multiple cycles is plotted, comparing the silicon-doped monolith and silicon particles doped via conventional slurry processing methods.

[0050] Figure 3 is a flow chart illustrating the formation of polyimide-derived carbon aerogels.

[0051] Figure 4 The density of carbonized polyimide (CPI) composites is plotted as a function of compressed thickness (initial thickness approximately 250 μm).

[0052] Figure 5 The density of the CPI composite is plotted as a function of compressed thickness (initial thickness approximately 580 microns).

[0053] Fig. 6A is a scanning electron microscope (SEM) image of the Si-doped, uncompressed PI aerogel (LS1).

[0054] Figure 6B is the SEM image of Si-doped compressed PI aerogel (LS2).

[0055] Figure 7 The discharge capacity (half-cell test, 0.1°C rate) of the compressed composites for each dopant (silicon, LS2; graphite; LG2) is depicted.

[0056] Figure 8 The surface area and micropore area relationship of silicon content in the CPI monolith is depicted.

[0057] Fig. 9 The pore size distribution of the Si-doped CPI ensemble is depicted.

[0058] Fig.10 The discharge capacity of the CPI composite at cycle 5 is plotted as a function of Si content.

[0059] Fig.11A SEM image of CPI composite with Si loading of 27% in the composite.

[0060] Fig. 11B is the SEM image of the CPI composite with 46% Si loading in the composite.

[0061] Fig. 11C is the SEM image of the CPI composite with 64% Si loading in the composite.

[0062] Fig. 12A The cycling capacity based on 27% Si content (S27) is depicted.

[0063] Fig. 12B Depicted with Fig. 12A Compared to the cycling capacity of the electrode.

[0064] Fig. 12C The cycling capacity based on 46% Si content (S46) is depicted.

[0065] Fig.12D Depicted with Fig. 12C Compared to the cycling capacity of the electrode.

[0066] Fig.12E The cycling capacity based on 64% Si content (S64) is depicted.

[0067] Fig.12F Depicted with Fig.12E Compared to the cycling capacity of the electrode.

[0068] Fig.13A is a SEM image of a CPI composite material having a thickness of about 337 microns.

[0069] Fig. 13B is a SEM image of a CPI composite material with a thickness of about 180 μm.

[0070] Fig.14A The discharge capacity based on the electrode weight (thickness about 323 μm) is plotted.

[0071] Fig. 14B The discharge capacity based on the electrode weight is plotted (thickness approximately 170 μm).

[0072] Fig.15A Pre-thermal SEM image of CPI composite (C45) prepared without dispersant.

[0073] Fig. 15B for Fig.15A SEM images of the composites after pyrolysis.

[0074] Fig.16A is a SEM image of a CPI composite prepared without using a dispersant (C45-control).

[0075] Fig. 16B is a SEM image of a CPI composite (B45) prepared with BYK 384 dispersant.

[0076] Fig. 16C is a SEM image of the CPI composite (P45) prepared with Pluronic F87 dispersant.

[0077] Fig.17A Depicted Fig.16A Discharge capacity of the C45 composite material.

[0078] Fig. 17B Depicted Fig. 16B Discharge capacity of the B45 composite material.

[0079] Fig. 17C Depicted Fig. 16C Discharge capacity of the P45 composite material.

[0080] Fig.18 The density versus thickness of the P45 CPI composite is plotted.

[0081] Fig.19 The electrical conductivity versus density of the CPI composites doped with various Si levels is plotted.

[0082] Fig. 20 is a schematic diagram depicting the formation of polyamic acid.

[0083] Fig.21 Isotherms for four (4) CPI samples are depicted.

[0084] Fig. 22 Depicted Fig.21Pore ​​size distribution of CPI samples.

[0085] Fig.23 SEM image of MT material (uncompressed).

[0086] Fig.24 This is the SEM image of the MTC material (after compression).

[0087] Fig.25A Depicted are the cycling capacities based on Si content (left) and based on electrode (right) for compressed CPI samples.

[0088] Fig.25B Depicted are the cycling capacity based on Si content (left) and based on electrode (right) for non-compressed CPI samples.

[0089] Fig.26A Depicted are the cycling capacity based on silicon content (left) and based on electrode (right) for a compressed CPI sample containing 29 wt% silicon per total solids.

[0090] Fig.26B Depicted are the cycling capacities based on silicon content (left) and on the electrode (right) for a non-compressed CPI sample containing 29 wt% silicon per total solids.

[0091] Fig. 27 Depicts the infiltration of carbon fiber (10g / m 2 ) Properties and microscope photos of carbon / Si in .

[0092] Fig.28 Depicts the infiltration of carbon fiber (4g / m 2 ) Properties and micrographs of carbon / Si in .

[0093] Fig.29 Depicts the infiltration of carbon fiber (2g / m 2 ) Properties and micrographs of carbon / Si in .

[0094] Fig.30 The cycling capacity of carbon fiber reinforced C / Si based on Si content (left) and based on electrode (right) is depicted.

[0095] Fig.31 Depicted are the cycling capacities of cellulose fiber-reinforced C / Si based on Si content (left) and based on electrode (right).

[0096] Fig.32 is a SEM image of a thick composite (about 0.6 mm) in which Si and PI were mixed for 16 hours.

[0097] Fig.33 is a SEM image of a thin composite material (about 0.12 mm) in which Si and PI were mixed for 16 hours.

[0098] Fig.34 is the SEM image of the whole sample, in which Si and PI were mixed for 16 h.

[0099] Fig.35 These are SEM cross-sectional images of the C / Si monolith, where Si and PI were mixed for 16 hours in the left image and for 4-6 minutes in the right image.

[0100] Fig.36 These are SEM cross-sectional images of C / Si composites, where Si and PI were mixed for 16 hours in the left image and for 4-6 minutes in the right image.

[0101] Fig.37 The cycling capacity of non-compressed C / Si (mixed for 16 hours) is depicted based on Si content (left) and based on electrode (right).

[0102] Fig.38 The cycling capacity of compressed C / Si (mixed for 16 hours) is depicted based on Si content (left) and based on electrode (right).

[0103] Fig.39 Depicted is a compressed circular Si / C electrode fabricated on an aerogel using a die cutter.

[0104] Fig.40 The cycling capacity of non-compressed circular C / Si aerogels is depicted based on Si content (left) and based on electrode (right).

[0105] Fig.41 The cycling capacity of compressed circular C / Si aerogels based on Si content (left) and based on electrode (right) are depicted.

[0106] Fig.42 Depicted is a C / Si aerogel sample produced from a PF / Si aerogel.

[0107] Fig.43 Depicted is a SEM image of a C / Si aerogel (produced from a PF / Si aerogel).

[0108] Fig.44 The cycling capacity of the PF aerogel composite with Si based electrodes is depicted.

[0109] Fig.45 The effect of silicon content on the Young's modulus of samples tested using the nanoindentation method is depicted.

[0110] Fig.46 The effect of density on Young’s modulus tested using nanoindentation method is depicted.

[0111] Fig.47is a SEM image of a granular C / Si aerogel sample according to an embodiment disclosed herein.

[0112] Fig.48 Depicted are the cycling performance of electrodes including CPI silica beads according to embodiments disclosed herein. DETAILED DESCRIPTION

[0113] In the following detailed description of the present invention, reference is made to the accompanying drawings, which form a part of the present invention and in which are shown by way of illustration specific embodiments in which the present invention may be implemented. It should be understood that other embodiments may be utilized and structural changes may be made without departing from the scope of the present invention.

[0114] As used in this specification and the appended claims, the singular forms "a", "an", and "the" include plural referents unless the content clearly dictates otherwise. As used in this specification and the appended claims, the term "or" is generally used in its sense including "and / or" unless the context clearly dictates otherwise.

[0115] As used herein, "about" means approximately or nearly, and in the context of a numerical value or range being described, refers to the numerical value ± 15%. In one embodiment, the term "about" may include conventional rounding according to the significant figures of the numerical value. In addition, the phrase "about 'x' to 'y'" includes "about 'x' to about 'y'".

[0116] In the context of the present disclosure, the term "aerogel" or "aerogel material" refers to a gel comprising a framework of interconnected structures, having a corresponding network of interconnected pores integrated within the framework, and containing a gas such as air as a dispersed interstitial medium; and characterized by having the following physical and structural properties attributable to aerogels (based on the nitrogen porosity test): (a) an average pore size ranging from about 2 nm to about 100 nm; (b) a porosity of at least 80% or more; and (c) a surface area of ​​about 20 m 2 / g or more. It is understood that the inclusion of additives, such as reinforcing materials or electrochemically active materials, may reduce the porosity of the resulting aerogel composite. Densification may also reduce the porosity of the resulting aerogel composite. This will become clearer as this specification continues.

[0117] Thus, aerogel materials of the present disclosure include any aerogel or other open-cell compound that satisfies the defining elements set forth in the preceding paragraphs, including compounds that may otherwise be classified as xerogels, cryogels, ambigels, microporous materials, and the like.

[0118] In the context of the present disclosure, the term "framework" or "framework structure" refers to a network of interconnected oligomers, polymers or colloidal particles that form the solid structure of a gel or aerogel. The polymers or particles that make up the framework structure typically have a diameter of about 100 angstroms. However, the framework structure of the present disclosure may also include a network of interconnected oligomers, polymers or colloidal particles of all diameter sizes that form the solid structure in the gel or aerogel.

[0119] In the context of the present disclosure, the term "aerogel composition" refers to any composite material that includes an aerogel material as a component of the composite material. Examples of aerogel compositions include, but are not limited to, fiber-reinforced aerogel composites; aerogel composites that include additive elements such as opacifiers and electrochemically active materials; aerogel foam composites; aerogel polymer composites; and composites that incorporate aerogel particles, granules, pellets, beads or powders into a solid or semi-solid material, such as an adhesive, resin, cement, foam, polymer or similar solid material.

[0120] In the context of the present disclosure, the term "enhanced aerogel composition" refers to an aerogel composition comprising a reinforcing phase in an aerogel material, which is not a part of an aerogel framework or can be modified in a covalently bonded manner to an aerogel framework. The reinforcing phase can be any material that provides increased flexibility, elasticity, conformability or structural stability for an aerogel material. Examples of well-known reinforcing materials include, but are not limited to, open-cell foam reinforcing materials, closed-cell foam reinforcing materials, open-cell membranes, honeycomb reinforcing materials, polymer reinforcing materials and fiber reinforced materials, such as discrete fibers, woven materials, nonwoven materials, cotton wool, nets, pads and felts. In addition, reinforcing agents can be combined with one or more other reinforcing materials and can be continuously oriented in the entire or limited preferred portion of the composition. In other embodiments, if the aerogel material and / or the aerogel framework itself is structurally stable (i.e., self-sustaining), reinforcing phases may not be used at all. As this specification continues, this self-sustaining property of some carbon aerogels will become clearer.

[0121] In the context of the present disclosure, the term "wet gel" refers to a gel in which the mobile interstitial phase within the network of interconnected pores consists primarily of a liquid phase (e.g., a conventional solvent), a liquefied gas (e.g., liquid carbon dioxide), or a combination thereof. Aerogels typically require first producing a wet gel, followed by processing and extraction to replace the mobile interstitial liquid phase in the gel with air or other gases. Examples of wet gels include, but are not limited to, alcohol gels, hydrogels, keto gels, carbon gels, and any other wet gels known to those skilled in the art.

[0122] In the context of the present disclosure, the term "additive" or "additive element" refers to a material that can be added to the composition before, during, or after the production of the composition. Additives can be added, for example, to change or improve desired properties in the aerogel composition, or to offset or mitigate undesirable properties in the aerogel composition. Additives are typically added to the aerogel composition before or during gelation. Additives can also be added to the aerogel composition by atomic layer deposition or chemical vapor deposition (CVD). A specific example of an additive is an electrochemically active material, such as silicon, for example silicon particles.

[0123] In the context of the present disclosure, the term "silicon particles" refers to silicon or silicon-based materials having a range of particle sizes suitable for use with the aerogel compositions disclosed herein. The silicon particles of the present disclosure may be nanoparticles, such as particles having two or three dimensions in the range of about 1 nm to about 150 nm. The silicon particles of the present disclosure may be fine particles, such as micron-sized particles having two or three dimensions (e.g., diameters of substantially spherical particles) in the range of about 150 nm to about 10 microns or more. For example, the two or three dimensions (e.g., diameters of substantially spherical particles) of the silicon particles of the present disclosure may be about 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 500 nm, 1 micron, 1.5 microns, 2 microns, 3 microns, 5 microns, 10 microns, 20 microns, 40 microns, 50 microns, 100 microns, or in the range between any two of these values. In some embodiments, the silicon particles may be monodisperse or substantially monodisperse. In other embodiments, the silicon particles may have a particle size distribution. In the context of the present disclosure, the size of the silicon particles is provided based on the median value of the particle size distribution, i.e., D50. The silicon particles of the present disclosure may be silicon wire, crystalline silicon, amorphous silicon, silicon alloy, silicon oxide (SiO x ), coated silicon such as carbon-coated silicon, and any combination of the silicon particle materials disclosed herein.

[0124] In the context of the present disclosure, the term "self-supporting" refers to the ability of an aerogel material or composition to have flexibility and / or elasticity based primarily on the physical properties of the aerogel. The self-supporting aerogel materials or compositions of the present disclosure can be distinguished from other aerogel materials (e.g., coatings) that rely on an underlying substrate or reinforcement material to provide flexibility and / or elasticity to the material.

[0125] In the context of this disclosure, the term "density" refers to a measurement of the mass per unit volume of an aerogel material or composition. The term "density" generally refers to the true density of an aerogel material, as well as the bulk density of an aerogel composition. Density is generally reported as kg / m 3Or g / cc. The density of an aerogel material or composition can be determined by methods known in the art, including, but not limited to: Standard Test Methods for Dimensions and Density of Preformed Block and Panel Insulation Materials (ASTM C303, ASTM International, West Conshohocken, Pa.); Standard Test Methods for Thickness and Density of Blanket or Batt Insulation Materials (ASTM C167, ASTM International, West Conshohocken, Pa.); or Determination of Apparent Density of Preformed Tube Insulation Materials (ISO 18098, International Organization for Standardization, Switzerland). In the context of this disclosure, density measurements are obtained according to the ASTM C167 standard unless otherwise stated. Preferably, the aerogel material or composition of the present disclosure has a density of about 1.50 g / cc or less, about 1.40 g / cc or less, about 1.30 g / cc or less, about 1.20 g / cc or less, about 1.10 g / cc or less, about 1.00 g / cc or less, about 0.90 g / cc or less, about 0.80 g / cc or less, about 0.70 g / cc or less, about 0.60 g / cc or less, about 0.50 g / cc or less, about 0.40 g / cc or less, about 0.30 g / cc or less, about 0.20 g / cc or less, about 0.10 g / cc or less, or in a range between any two of these values, for example, from about 0.15 g / cc to 1.5 g / cc, or more specifically, from 0.50 g / cc to 1.5 g / cc.

[0126] According to certain embodiments, the production of aerogels generally includes the following steps: i) forming a solution containing a gel precursor; ii) forming a gel from the solution; and iii) extracting a solvent from the gel material to obtain a dry aerogel material. According to certain embodiments, the production of aerogel beads follows the general process of aerogel production and generally includes the following steps: i) forming a solution containing a gel precursor; ii) dispersing the gel precursor in a medium immiscible with the gel precursor; iii) forming gel beads from the gel precursor solution in the immiscible medium; iv) removing the gel beads from the medium; and v) extracting the solvent from the gel beads to obtain a dry aerogel material. These methods are discussed in more detail below, particularly in the context of forming organic aerogels such as polyimide aerogels. However, the specific embodiments and descriptions provided herein are not intended to limit the present disclosure to any specific type of aerogel and / or preparation method. The present disclosure may include any aerogel formed by any relevant preparation method known to those skilled in the art.

[0127] An exemplary solution for producing a silica aerogel is formed by combining at least one gelling precursor with a solvent. Suitable solvents for forming the solution include lower alcohols having 1 to 6 carbon atoms (preferably 2 to 4 carbon atoms), although other solvents known to those skilled in the art may also be used. Examples of useful solvents include, but are not limited to, methanol, ethanol, isopropanol, ethyl acetate, ethyl acetoacetate, acetone, methylene chloride, tetrahydrofuran, and the like. Multiple solvents may also be combined to achieve a desired dispersion level or to optimize the properties of the gel material. Therefore, the selection of the optimal solvent for the polymerization and gel formation steps depends on the specific precursors, fillers, and additives incorporated into the solution; as well as the target processing conditions for gelation and liquid phase extraction, and the desired properties of the final aerogel material.

[0128] An exemplary solution for producing polyimide aerogels is formed by combining at least one diamine and at least one dianhydride in one or more common polar aprotic solvents. Additional details on the formation of polyimide gels / aerogels can be found in the following references: Rhine et al., U.S. Patent Nos. 7,074,880 and 7,071,287; Suzuki et al., U.S. Patent No. 6,399,669; Leventis et al., U.S. Patent No. 9,745,198; Leventis et al., Polyimide Aerogels by Ring-Opening Metathesis Polymerization (ROMP), Chem. Mater. 2011, 23, 8, 2250-2261; Leventis et al, Isocyanate-Derived Organic Aerogels: Polyureas, Polyimides, Polyamides, MRS Proceedings, 1306 (2011), Mrsf10-1306-bb03-01.doi:10.1557 / opl.2011.90; Chidambareswarapattar et al, One-step room-temperature synthesis of fibrous polyimide aerogels from anhydrides and isocyanates and conversion to isomorphic carbons, J.Mater.Chem., 2010, 20, 9666-9678; Guo et al, Polyimide Aerogels Cross-Linked through AmineFunctionalized Polyoligomeric Silsesquioxane, ACS Appl.Mater.Interfaces 2011,3,546-552; Nguyen et al,Development of High Temperature,Flexible PolyimideAerogels,American Chemical Society,Proceedings published in 2011;Meador et al,Mechanically Strong,Flexible Polyimide Aerogels Cross-Linked with AromaticTriamine,ACS Appl.Mater.Interfaces,2012,4(2),pp 536-544; Meador et al., Polyimide Aerogels with Amide Cross-Links: A Low Cost Alternative for Mechanically Strong Polymer Aerogels, ACS Appl.Mater.Interfaces 2015, 7, 1240-1249; Pei et al, Preparation and Characterization of Highly Cross-Linked Polyimide Aerogels Based on Polyimide Containing Trimethoxysilane Side Groups, Langmuir 2014, 30, 13375-13383, each of which is incorporated herein by reference in its entirety. Instead of or in addition to diamines or combinations thereof, triamines, tetraamines, pentamines, hexamines, etc. may also be used to optimize the properties of the gel material. Instead of or in addition to dianhydrides or combinations thereof, trianhydrides, tetraanhydrides, pentaanhydrides, hexaanhydrides may also be used to optimize the properties of the gel material. Dehydrating agents and catalysts may be added to the solution to initiate and drive imidization. .

[0129] The solution may include additional co-gel precursors as well as filler materials and other additives. The filler materials and other additives may be dispensed into the solution at any point before or during gel formation. The filler materials and other additives may also be incorporated into the gel material after gelation by various techniques known to those skilled in the art. Preferably, the solution comprising the gelling precursor, solvent, catalyst, water, filler materials and other additives is a homogeneous solution that is capable of effectively forming a gel under suitable conditions.

[0130] Once the solution is formed and optimized, the gel-forming components in the solution can be converted into a gel material. The process of converting the gel-forming components into a gel material includes an initial gel formation step, in which the gel solidifies to the gel point of the gel material. The gel point of the gel material can be regarded as the point at which the gelled solution exhibits resistance to flow and / or forms a substantially continuous polymer framework throughout its volume. A range of gel formation techniques are known to those skilled in the art. Examples include, but are not limited to: keeping the mixture in a quiescent state for a sufficient period of time; adjusting the concentration of the catalyst; adjusting the temperature of the solution; directing a certain form of energy to the mixture (ultraviolet light, visible light, infrared, microwave, ultrasound, particle radiation, electromagnetic); or a combination thereof.

[0131] The process of forming gel beads from a gel solution may include mixing the solution with a medium (e.g., a dispersion medium) that is immiscible with the solution. For example, silicone oil or mineral oil may be used as a dispersion medium. The gel solution may be added (e.g., by pouring) or otherwise mixed with an immiscible dispersion medium. Before or during the process of converting the gel-forming components into a gel material, the formation of droplets (e.g., beads) may be promoted by stirring (e.g., by mixing) the combined dispersion medium and gel precursor solution. For example, the combination of a dispersion medium and a gel precursor may form an emulsion with a gel precursor solution as a dispersed phase. Exemplary methods of gel bead production may be found in U.S. Patent Application Publication No. 2006 / 0084707 to Ou et al., which is incorporated herein by reference in its entirety.

[0132] Spherical droplets of gel precursor are formed in the dispersion medium due to interfacial tension. The droplets gel and strengthen in the dispersion medium (e.g., silicone oil). Agitation of the mixture is usually used to prevent the droplets from agglomerating. Heat or radiation can also be provided to the dispersion medium to induce or enhance the gelation of the droplets or to enhance the gel beads so that they are strong enough to resist collisions. The production capacity of gel beads in a given space depends on the precise control of the droplet gelation process.

[0133] The method also includes removing the gel beads from a dispersion medium (e.g., silicone oil). The gel beads are filtered from the dispersion medium and then washed or rinsed with a fluid, such as an alcohol such as ethanol, methanol, isopropanol, or a higher alcohol. A basic requirement of the rinse fluid is that it can remove oil (or other dispersion medium) without chemically reacting with the gel. After removing excess silicone oil, the gel beads can be placed in a solvent for aging, as discussed in more detail below. For example, the gel beads can be aged in ethanol. The gel beads can use a supercritical fluid drying method as discussed herein to remove interstitial solvents. They can also be dried under ambient conditions to make dry gels. As discussed in more detail below, the dried gel beads (e.g., aerogels or dry gel beads) can be heat treated and carbonized. In an exemplary embodiment, the gel beads are substantially spherical.

[0134] The process of converting the gel-forming components into a gel material may also include an aging step (also known as curing) prior to liquid extraction. Aging the gel material after reaching its gel point can further strengthen the gel framework by increasing the number of crosslinks within the network. The duration of gel aging can be adjusted to control various properties within the resulting aerogel material. This aging procedure can be used to prevent potential volume loss and shrinkage during liquid extraction. Aging can include: keeping the gel (before extraction) in a static state for a long time; keeping the gel at an elevated temperature; adding a crosslinking promoting compound; or any combination thereof. The preferred temperature for aging is generally about 10°C to about 200°C. Aging of the gel material generally continues until liquid extraction of the wet gel material.

[0135] The time period for converting the gel-forming material to the gel material includes the duration of the initial gel formation (from the start of gelation to the gel point) and the duration of any subsequent solidification and aging of the gel material prior to liquid phase extraction (from the gel point to the start of liquid phase extraction). The total time for converting the gel-forming material to the gel material is generally from about 1 minute to several days, preferably about 30 hours or less, about 24 hours or less, about 15 hours or less, about 10 hours or less, about 6 hours or less, about 4 hours or less, about 2 hours or less, about 1 hour or less, about 30 minutes or less, or about 15 minutes or less.

[0136] The resulting gel material can be washed in a suitable secondary solvent to replace the primary reaction solvent present in the wet gel. Such a secondary solvent can be a linear monohydric alcohol having 1 or more aliphatic carbon atoms, a dihydric alcohol having 2 or more carbon atoms, a branched alcohol, a cyclic alcohol, an alicyclic alcohol, an aromatic alcohol, a polyol, an ether, a ketone, a cyclic ether or a derivative thereof.

[0137] Once the gel material has been formed and processed, the liquid phase of the gel can then be at least partially extracted from the wet gel using extraction methods (including processing and extraction techniques) to form an aerogel material. Liquid phase extraction plays an important role in the characteristics of the engineered aerogel, such as porosity and density, and related properties, such as thermal conductivity, among other factors. Typically, an aerogel is obtained when the liquid phase is extracted from the gel in a manner that causes low shrinkage to the porous network and framework of the wet gel.

[0138] Aerogels are typically formed by removing a liquid mobile phase from a gel material at a temperature and pressure near or above the critical point of the liquid mobile phase. Once the critical point is reached (near critical) or exceeded (supercritical) (i.e., the pressure and temperature of the system are at or above the critical pressure and critical temperature, respectively), a new supercritical phase appears in the fluid that is different from the liquid or gas phase. The solvent can then be removed without introducing a liquid-vapor interface, capillary pressure, or any mass transfer limitations typically associated with liquid-vapor boundaries. In addition, the supercritical phase is typically more miscible with organic solvents and therefore has better extraction capabilities. Co-solvents and solvent exchange are also commonly used to optimize supercritical fluid drying processes.

[0139] If evaporation or extraction occurs below the supercritical point, capillary forces generated by the evaporation of the liquid can cause shrinkage and pore collapse within the gel material. Maintaining the mobile phase near or above the critical pressure and temperature during the solvent extraction process can reduce the negative effects of such capillary forces. In certain embodiments of the present disclosure, the use of near-critical conditions just below the critical point of the solvent system can allow the production of aerogel materials or compositions with sufficiently low shrinkage to produce a commercially viable final product.

[0140] A variety of additional aerogel extraction techniques are known in the art, including a range of different methods using supercritical fluids in drying aerogels, as well as ambient drying techniques. For example, Kistler (J. Phys. Chem. (1932) 36: 52-64) describes a simple supercritical extraction method in which the gel solvent is maintained above its critical pressure and temperature, thereby reducing evaporative capillary forces and maintaining the structural integrity of the gel network. U.S. Patent No. 4,610,863 describes an extraction method in which the gel solvent is exchanged with liquid carbon dioxide and then extracted under conditions in which the carbon dioxide is in a supercritical state. U.S. Patent No. 6,670,402 teaches the extraction of a liquid phase from a gel by rapid solvent exchange, which produces aerogels by injecting supercritical (rather than liquid) carbon dioxide into an extractor that has been preheated and pre-pressurized to substantially supercritical conditions or higher. U.S. Patent No. 5,962,539 describes a method of obtaining an aerogel from a polymer material in the form of a sol-gel in an organic solvent by exchanging the organic solvent for a fluid having a critical temperature below the decomposition temperature of the polymer and supercritically extracting the fluid / sol-gel. U.S. Patent No. 6,315,971 discloses a method of producing a gel composition comprising: drying a wet gel comprising gel solids and a desiccant to remove the desiccant under drying conditions sufficient to reduce shrinkage of the gel during drying. U.S. Patent No. 5,420,168 describes a method of making a resorcinol / formaldehyde aerogel using a simple air drying procedure. U.S. Patent No. 5,565,142 describes a drying technique in which the gel surface is modified to be stronger and more hydrophobic so that the gel framework and pores can resist collapse during ambient drying or subcritical extraction. Other examples of extracting a liquid phase from an aerogel material can be found in U.S. Patent Nos. 5,275,796 and 5,395,805.

[0141] A preferred embodiment of extracting the liquid phase from the wet gel uses supercritical conditions of carbon dioxide, including, for example: first, substantially exchanging the primary solvent present in the gel pore network with liquid carbon dioxide; then, heating the wet gel (usually in an autoclave) above the critical temperature of carbon dioxide (about 31.06°C) and increasing the system pressure to a pressure greater than the critical pressure of carbon dioxide (about 1070 psig). The pressure around the gel material can fluctuate slightly to facilitate the removal of the supercritical carbon dioxide fluid from the gel. The carbon dioxide can be recycled through the extraction system to facilitate the continued removal of the primary solvent from the wet gel. Finally, the temperature and pressure are slowly restored to ambient conditions to produce a dry aerogel material. The carbon dioxide can also be pretreated to a supercritical state before being injected into the extraction chamber. In other embodiments, any suitable mechanism can be used for extraction, such as changing the above-mentioned pressure, time and solvent.

[0142] In certain embodiments of the present invention, the dried polyimide aerogel composition may be subjected to one or more heat treatments for a duration of 3 hours or more, 10 seconds to 3 hours, 10 seconds to 2 hours, 10 seconds to 1 hour, 10 seconds to 45 minutes, 10 seconds to 30 minutes, 10 seconds to 15 minutes, 10 seconds to 5 minutes, 10 seconds to 1 minute, 1 minute to 3 hours, 1 minute to 1 hour, 1 minute to 45 minutes, 1 minute to 30 minutes, 1 minute to 15 minutes, 1 minute to 5 minutes, 10 minutes to 3 hours, 10 minutes to 1 hour, 10 minutes to 45 minutes, 10 minutes to 30 minutes, 10 minutes to 15 minutes, 30 minutes to 3 hours, 30 minutes to 1 hour, 30 minutes to 45 minutes, 45 minutes to 3 hours, 45 minutes to 90 minutes, 45 minutes to 60 minutes, 1 hour to 3 hours, 1 hour to 2 hours, 1 hour to 90 minutes, or in a range between any two of these values.

[0143] In certain embodiments, the present invention relates to the formation of nanoporous carbon-based scaffolds or structures (e.g., carbon aerogels) and use as electrode materials in energy storage devices, such as as the main anode material in LIBs. For example, the pores of the nanoporous scaffolds are designed, organized and structured to accommodate particles of silicon or other metalloids or metals, and the expansion of such particles in LIBs upon lithiation. Alternatively, the pores of the nanoporous scaffolds can be filled with sulfides, hydrides, any suitable polymers or other additives, where it is beneficial to contact the additives with the conductive material (i.e., the scaffold / aerogel) to provide a more effective electrode. Figure 1 A general process for utilizing silicon-doped carbon aerogels in battery applications can be seen in .

[0144] To further expand the exemplary applications within LIBs, when carbon aerogel materials are used as the primary anode material as in certain embodiments of the present invention, the aerogel nanoporous structure has a narrow pore size distribution and provides high conductivity, high mechanical strength, and morphology and sufficient pore volume (at final density) to accommodate a high weight percentage of silicon particles and their expansion. Structurally, certain embodiments of the present invention have a fibrous morphology with strut sizes that produce the aforementioned narrow pore size distribution, high pore volume, and enhanced connectivity.

[0145] In additional or alternative embodiments, the carbon aerogel itself acts as a current collector due to its conductivity and mechanical strength, thus, in preferred embodiments, eliminating the need for a specific current collector on the anode side (when the anode is formed of a carbon aerogel). It is worth noting that in conventional LIBs, copper foil is connected to the anode as its current collector. However, depending on the application of the carbon aerogel, removing one or both of these components provides additional space for more electrode materials, resulting in a larger capacity of the battery / single electrode and a greater overall energy density of the packaged battery system. However, in certain embodiments, the existing current collector can be integrated with the anode materials of various other embodiments to enhance the current collection capacity or capacity of the copper foil or aluminum foil.

[0146] In certain embodiments, a nanoporous carbon-based scaffold structure, in particular a carbon aerogel, can be used as a conductive network or current collector on the anode side of an energy storage device. The fully interconnected carbon aerogel network is filled with an electrochemically active substance, wherein the electrochemically active substance is in direct contact with or physically connected to the carbon network. The loading of the electrochemically active substance is adjusted relative to the pore volume and porosity to obtain a high and stable capacity and improved safety of the energy storage device. When used on the anode side, the electrochemically active substance may include, for example, silicon, graphite, lithium or other metalloids or metals. In another embodiment, the anode may comprise a nanoporous carbon-based scaffold or structure, in particular a carbon aerogel.

[0147] In the context of the present disclosure, the term "no current collector" means that there is no specific current collector directly connected to the electrode. As mentioned above, in conventional LIBs, copper foil is usually connected to the anode as its current collector. According to an embodiment of the present invention, an electrode formed by a nanoporous carbon-based scaffold or structure (e.g., carbon aerogel) can be a stand-alone structure or otherwise have the ability to be without a current collector because the scaffold or structure itself acts as a current collector due to its high conductivity. In an electrochemical cell, a current collector-free electrode can be connected to form a circuit by embedding a solid, mesh, or woven sheet in a solution step for preparing a continuous porous carbon; or by brazing, welding, or metal deposition leads to a portion of the porous carbon surface. Other mechanisms for contacting carbon with the rest of the system are also considered herein. In an alternative embodiment, the nanoporous carbon-based scaffold or structure, in particular the carbon aerogel, can be disposed on a dedicated current collector substrate (e.g., copper foil, aluminum foil, etc.) or otherwise connected to a dedicated current collector substrate. In this case, a conductive adhesive can be used and different pressures can be applied to attach the carbon aerogel to a solid current collector.

[0148] Furthermore, it is contemplated herein that the nanoporous carbon-based scaffold or structure, in particular the carbon aerogel, may be in the form of a monolithic structure. When monolithic in nature, the carbon aerogel does not require any binder; in other words, the anode may be binder-free. As used herein, the term "monolithic" refers to an aerogel material wherein a majority (by weight) of the aerogel included in the aerogel material or composition is in the form of a single continuous interconnected aerogel nanostructure. Monolithic aerogel materials include aerogel materials that are initially formed as having a single interconnected gel or aerogel nanostructure, but which may subsequently be fractured, broken or segmented into non-unitary aerogel nanostructures. Monolithic aerogels may be in the form of freestanding structures or reinforced (fiber or foam) materials. In contrast, taking silicon lithiation as an example, silicon incorporated into a monolithic aerogel may be utilized more efficiently relative to theoretical capacity than the same amount of silicon incorporated into a slurry using conventional processes (see Figure 2 ).

[0149] Monolithic aerogel materials are distinguished from particulate aerogel materials. The term "particulate aerogel material" refers to an aerogel material in which the majority (by weight) of the aerogel included in the aerogel material is in the form of particles, granules, pellets, beads or powders, which can be combined together (i.e., by a binder, such as a polymer binder) or compressed together, but lack interconnected aerogel nanostructures between individual particles. In general, this form of aerogel material will be referred to as having a powder or granular form (as opposed to a monolithic form). It should be noted that although the individual particles of the powder have a single structure, the individual particles are not considered to be monolithic in this article. Aerogel powders are integrated into electrochemical cells, typically a paste or slurry is prepared from the powder, cast and dried onto a substrate, and calendering may optionally be included.

[0150] Particulate aerogel materials (e.g., aerogel beads) provide certain advantages. For example, in LIB anodes and anode manufacturing processes, particulate materials according to embodiments disclosed herein can be used as direct substitutes for other materials such as graphite. Due to the short diffusion paths within the particulate materials, particulate materials according to embodiments disclosed herein can also provide improved lithium ion diffusion rates. Particulate materials according to embodiments disclosed herein can also allow electrodes to have optimized packing density, such as by adjusting particle size and packing arrangement. Due to inter-particle and intra-particle porosity, particulate materials according to embodiments disclosed herein can also provide improved access to silicon.

[0151] In the context of the present disclosure, the term "binder-less" or "binder-free" (or its derivatives) refers to a material that is essentially free of a binder or adhesive to hold the material together. For example, a monolithic nanoporous carbon material is binder-free because its framework is formed as a single continuous interconnected structure. The advantages of being binder-free include avoiding any effects of a binder, such as on conductivity and pore volume. On the other hand, aerogel particles require a binder to be bound together to form a larger functional material; such a larger material is not considered a monolithic material herein. In addition, this "binder-free" term does not exclude all uses of binders. For example, a monolithic aerogel according to the present invention can be fixed to another monolithic aerogel or non-aerogel material by placing an adhesive or adhesive on the major surface of the aerogel material. In this way, the adhesive is used to make a laminated composite, but the adhesive does not have the function of maintaining the stability of the monolithic aerogel framework itself.

[0152] In addition, the monolithic polymer aerogel material or composition disclosed herein can be compressed to a strain of up to 95% without significantly damaging or cracking the aerogel framework, while making the aerogel dense and minimizing the porosity. In certain embodiments, the compressed polymer aerogel material or composition is subsequently carbonized using the various methods described herein to form a nanoporous carbon material. It is understood that the amount of compression affects the thickness of the resulting carbon material, wherein the thickness has an effect on the capacity, which will become clearer as this specification continues. The embodiments described below will illustrate the different thicknesses formed and considered by the present invention, wherein the thickness can be adjusted based on compression. Therefore, the thickness of the composite material (usually compressed) can be about 10-1000 microns, or any narrower range therein based on the benefits desired for the final composite material. The present invention also contemplates carbon aerogels in powder or granular form, where there may be a need for a binder and to optimize the particle size. The particle size range can be about 1-50 microns.

[0153] Nanoporous carbon (such as carbon aerogel) according to the present invention can be formed by any suitable organic precursor material. The example of such material includes but is not limited to RF, PF, PI, polyamide, polyacrylate, polymethyl methacrylate, acrylate oligomer, polyoxyalkylene, polyurethane, polyphenol, polybutane, trialkoxysilyl-terminated polydimethylsiloxane, polystyrene, polyacrylonitrile, polyfurfural, melamine-formaldehyde, cresol formaldehyde, phenol furfural, polyether, polyol, polyisocyanate, polyhydroxybenzene, polyvinyl alcohol dialdehyde, polycyanurate, polyacrylamide, various epoxy resins, agar, agarose, chitosan and their combinations and derivatives. Any precursor of these materials can be used to produce and use the resulting material. In an exemplary embodiment, carbon aerogel is formed by pyrolysis / carbonized polyimide-based aerogel, i.e., the polymerization of polyimide. Even more specifically, polyimide-based aerogels may be produced using one or more of the methods described in US Pat. Nos. 7,071,287 and 7,074,880 to Rhine et al., for example by imidization of poly(amic) acids and drying the resulting gel using a supercritical fluid. Other suitable methods for producing polyimide aerogels (and carbon aerogels derived therefrom) are also contemplated herein, such as those described in the following references: U.S. Patent No. 6,399,669 to Suzuki et al.; U.S. Patent No. 9,745,198 to Leventis et al.; Leventis et al., Polyimide Aerogels by Ring-Opening Metathesis Polymerization (ROMP), Chem. Mater. 2011, 23, 8, 2250-2261; Leventis et al., Isocyanate-Derived Organic Aerogels: Polyureas, Polyimides, Polyamides, MRS Proceedings, 1306 (2011), Mrsf10-1306-bb03-01.doi:10.1557 / opl.2011.90; Chidambareswarapattar et al., One-step room-temperature synthesis of fibrouspolyimide aerogels from anhydrides and isocyanates and conversion toisomorphic carbons,J.Mater.Chem.,2010,20,9666-9678;Guo et al,PolyimideAerogels Cross-Linked through Amine Functionalized PolyoligomericSilsesquioxane,ACS Appl.Mater.Interfaces 2011,3,546-552;Nguyen et al,Development of High Temperature,Flexible Polyimide Aerogels,American ChemicalSociety, Proceedings published in 2011; Meador et al, Mechanically Strong, Flexible Polyimide Aerogels Cross-Linked with Aromatic Triamine, ACSAppl.Mater.Interfaces, 2012, 4(2), pp 536-544; Meador et al., Polyimide Aerogels with Amide Cross-Links: ALow Cost Alternative for Mechanically Strong PolymerAerogels, ACS Appl.Mater.Interfaces 2015,7,1240-1249; Pei et al. al, Preparation and Characterization of Highly Cross-Linked Polyimide Aerogels Based on Polyimide Containing Trimethoxysilane Side Groups, Langmuir 2014, 30, 13375-13383. The resulting polyimide aerogel is then pyrolyzed to form a polyimide-derived carbon aerogel. .

[0154] The carbon aerogel (e.g., polyimide-derived carbon aerogel) according to an exemplary embodiment of the present disclosure may have a residual nitrogen content of at least about 4 wt%. For example, the carbon aerogel according to the embodiments disclosed herein may have a residual nitrogen content of at least about 0.1 wt%, at least about 0.5 wt%, at least about 1 wt%, at least about 2 wt%, at least about 3 wt%, at least about 4 wt%, at least about 5 wt%, at least about 6 wt%, at least about 7 wt%, at least about 8 wt%, at least about 9 wt%, at least about 10 wt%, or within a range between any two of these values.

[0155] In certain embodiments of the present disclosure, the dried polymerized aerogel composition may be subjected to a treatment temperature of 200° C. or more, 400° C. or more, 600° C. or more, 800° C. or more, 1000° C. or more, 1200° C. or more, 1400° C. or more, 1600° C. or more, 1800° C. or more, 2000° C. or more, 2200° C. or more, 2400° C. or more, 2600° C. or more, 2800° C. or more, or a range between any two of these values ​​to carbonize the organic (e.g., polyimide) aerogel. Without being bound by theory, it is contemplated herein that the conductivity of the aerogel composition increases with increasing carbonization temperature.

[0156] In the context of the present disclosure, the term "conductivity" refers to a measurement of the ability of a material to conduct an electric current or otherwise allow electrons to flow or flow therethrough. Conductivity is specifically measured as the conductance / susceptance / admittance of a material per unit size. It is usually recorded as S / m (Siemens / meter) or S / cm (Siemens / centimeter). The conductivity or resistivity of a material can be determined by methods known in the art, such as, but not limited to: online four-point resistivity (using a dual configuration test method of ASTM F84-99). In the context of the present disclosure, unless otherwise stated, the measured value of conductivity is obtained according to ASTM F84-the measured value of resistivity (R) obtained by measuring the voltage (V) divided by the current (I). In certain embodiments, the conductivity of the aerogel material or composition of the present disclosure is about 10S / cm or greater, 20S / cm or greater, 30S / cm or greater, 40S / cm or greater, 50S / cm or greater, 60S / cm or greater, 70S / cm or greater, 80S / cm or greater, or in the range between any two of these values.

[0157] In the context of the present disclosure, the term "electrochemically active material" refers to an additive that can accept and release ions in an energy storage device. Taking LIB as an example, the electrochemically active material in the anode accepts lithium ions during charging and releases lithium ions during discharge. The electrochemically active material can be stabilized in the anode by direct / physical connection with the nanoporous carbon. In certain embodiments, the nanoporous carbon network forms an interconnected structure around the electrochemically active material. The electrochemically active material is connected to the nanoporous carbon at multiple points. An example of an electrochemically active material is silicon, which, as mentioned above, expands and may rupture or crack when lithiated. However, because silicon has multiple connection points with the nanoporous carbon (aerogel), silicon can be retained in the nanoporous structure and remain active, such as in a pore or otherwise surrounded by the structure, even when it is ruptured or cracked.

[0158] In the context of the present disclosure, the terms "compressive strength", "flexural strength" and "tensile strength" refer to the resistance of a material to rupture or cracking under compression, buckling or bending forces, and tension or pulling forces, respectively. These strengths are specifically measured as the amount of load / force per unit area that resists the load / force. It is usually recorded as pounds per square inch (psi), megapascals (MPa) or gigapascals (GPa). Among other factors, the compressive strength, flexural strength and tensile strength of a material jointly promote the structural integrity of the material, which is beneficial, for example, to withstand the volume expansion of silicon particles during lithiation in LIBs. With specific reference to Young's modulus, which is an indication of mechanical strength, the modulus can be determined by methods known in the art, such as, but not limited to: Standard Test Practice for Instrumented Indentation Tests (ASTM E2546, ASTM International, West Conshocken, PA); or Standardized Nanoindentation (ISO 14577, International Organization for Standardization, Switzerland). In the context of the present disclosure, measurements of Young's modulus are obtained according to ASTM E2546 and ISO 14577, unless otherwise stated. In certain embodiments, the Young's modulus of the aerogel materials or compositions of the present disclosure is about 0.2 GPa or greater, 0.4 GPa or greater, 0.6 GPa or greater, 1 GPa or greater, 2 GPa or greater, 4 GPa or greater, 6 GPa or greater, 8 GPa or greater, or in a range between any two of these values.

[0159] In the context of the present disclosure, the term "pore size distribution" refers to the statistical distribution or relative amount of each pore size within a sample volume of a porous material. A narrower pore size distribution means that the proportion of pores within the narrow pore size range is relatively large, thereby optimizing the amount of pores that can surround the electrochemically active material, thereby maximizing the use of the pore volume. In contrast, a wider pore size distribution means that the proportion of pores within the narrow pore size range is relatively small. Therefore, the pore size distribution is typically measured as a function of pore volume and recorded as a unit size of the half-height full width of the major peak in the pore size distribution graph. The pore size distribution of a porous material can be determined by methods known in the art, such as, but not limited to, surface area and porosity analyzers by nitrogen adsorption and desorption, from which the pore size distribution can be calculated. In the context of the present disclosure, unless otherwise stated, the measured values ​​of the pore size distribution are obtained according to this method. In certain embodiments, the aerogel materials or compositions of the present disclosure have a relatively narrow pore size distribution (full width at half maximum) of about 50 nm or less, 45 nm or less, 40 nm or less, 35 nm or less, 30 nm or less, 25 nm or less, 20 nm or less, 15 nm or less, 10 nm or less, 5 nm or less, or in a range between any two of these values.

[0160] In the context of the present disclosure, the term "pore volume" refers to the total volume of pores in a porous material sample. Pore volume is specifically measured as the volume of void space within a porous material, where the void space may be measurable and / or accessible to another material, such as an electrochemically active material, such as silicon particles. It is usually reported as cubic centimeters per gram (cm 3 / g or cc / g). The pore volume of a porous material can be determined by methods known in the art, such as, but not limited to, surface area and porosity analyzers by nitrogen adsorption and desorption, from which the pore volume can be calculated. In the context of the present disclosure, unless otherwise indicated, measurements of pore volume are obtained according to this method. In certain embodiments, the aerogel materials or compositions of the present disclosure (without incorporation of an electrochemically active material, such as silicon) have a relatively large pore volume of about 1 cc / g or greater, 1.5 cc / g or greater, 2 cc / g or greater, 2.5 cc / g or greater, 3 cc / g or greater, 3.5 cc / g or greater, 4 cc / g or greater, or within a range between any two of these values. In other embodiments, the aerogel materials or compositions of the present disclosure (with incorporated electrochemically active species, such as silicon) have a pore volume of about 0.3cc / g or greater, 0.6cc / g or greater, 0.9cc / g or greater, 1.2cc / g or greater, 1.5cc / g or greater, 1.8cc / g or greater, 2.1cc / g or greater, 2.4cc / g or greater, 2.7cc / g or greater, 3.0cc / g or greater, 3.3cc / g or greater, 3.6cc / g or greater, or in a range between any two of these values.

[0161] In the context of the present disclosure, the term "porosity" refers to the volume fraction of pores that do not contain another material (e.g., an electrochemically active material, such as silicon particles) bound to the pore walls. For the purpose of clarification and illustration, it should be noted that in the specific implementation of silicon-doped carbon aerogel as the primary anode material in LIBs, porosity refers to the void space after the silicon particles are included. Thus, when the anode is in a pre-lithiation state, the porosity can be, for example, about 10%-70% (to accommodate ion transport and silicon expansion), while when the anode is in a post-lithiation state, the porosity can be about 1%-50% (to accommodate ion transport). More generally, porosity can be determined by methods known in the art, such as, but not limited to, the ratio of the pore volume of the aerogel material to its bulk density. In the context of the present disclosure, unless otherwise stated, measurements of porosity are obtained according to this method. In certain embodiments, the porosity of the aerogel materials or compositions of the present disclosure is about 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or a range between any two of these values.

[0162] It should be noted that pore volume and porosity are different measures of the same property of the pore structure, i.e., the "empty space" within the pore structure. For example, when silicon is used as the electrochemically active species contained within the pores of the nanoporous carbon material, the pore volume and porosity refer to the "empty" space, i.e., the space not utilized by silicon and carbon. As will be seen, densification (e.g., by compression) of the pre-carbonized nanoporous material will also have an impact on properties such as pore volume and porosity.

[0163] In the context of the present disclosure, the term "pore size at the maximum peak from the distribution" refers to the value at the discernible peak on a graph illustrating the pore size distribution. The pore size at the maximum peak from the distribution is specifically measured as the pore size at which the maximum percentage of pores is formed. It is typically recorded as any unit length of pore size, such as microns or nm. The pore size at the maximum peak from the distribution can be determined by methods known in the art, such as, but not limited to, surface area and porosity analyzers by nitrogen adsorption and desorption, from which the pore size distribution can be calculated and the pore size at the maximum peak determined. In the context of the present disclosure, unless otherwise stated, the pore size measurement at the maximum peak from the distribution is obtained according to this method. In certain embodiments, the pore size from the maximum peak of the distribution of the aerogel materials or compositions of the present disclosure is about 150 nm or less, 140 nm or less, 130 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, 70 nm or less, 60 nm or less, 50 nm or less, 40 nm or less, 30 nm or less, 20 nm or less, 10 nm or less, 5 nm or less, 2 nm or less, or in a range between any two of these values.

[0164] In the context of the present disclosure, the term "pillar width" refers to the average diameter of the nanopillars, nanorods, nanofibers or nanowires that form an aerogel with a fibrous morphology. It is usually recorded as any unit length, such as micrometers or nm. The pillar width can be determined by methods known in the art, such as, but not limited to, scanning electron microscope image analysis. In the context of the present disclosure, unless otherwise stated, the measured value of the pillar width is obtained according to this method. In certain embodiments, the pillar width of the aerogel material or composition of the present disclosure is about 10nm or less, 9nm or less, 8nm or less, 7nm or less, 6nm or less, 5nm or less, 4nm or less, 3nm or less, 2nm or less or in the range between any two of these values. The exemplary range of pillar widths found in the following examples (especially in the SEM images in the figures) is about 2-5nm. Smaller pillar widths (such as these) allow a larger number of pillars to be present in the network and thereby contact with electrochemically active materials, which in turn allows more electrochemically active materials to be present in the composite material. This increases conductivity and mechanical strength.

[0165] In the context of the present disclosure, the term "fibrous morphology" refers to the structural morphology of nanoporous carbon (e.g., aerogel), including pillars, rods, fibers or filaments. For example, in one embodiment, the choice of solvent (such as dimethylacetamide (DMAC)) can affect the generation of this morphology. In addition, in certain embodiments, when the carbon aerogel is derived from a polyimide, the crystalline polyimide is produced by a polyimide that forms a linear polymer. It will be clearer in the following examples that it is surprising to observe that certain embodiments include a fibrous morphology as an interconnected polymer structure, wherein long linear structures are expected based on the known behavior of polyimide precursors. In contrast, the product form of the nanoporous carbon can alternatively be a granular property or powder, wherein the fibrous morphology of the carbon aerogel still exists. As the description continues and changes become clearer, the fibrous morphology can provide certain benefits that are superior to the granular morphology, such as mechanical stability / strength and conductivity, particularly when the nanoporous carbon is used in specific applications, such as as an anode material in LIB. It should be noted that this fibrous morphology can be found in both monolithic and powdered nanoporous carbons; in other words, monolithic carbon can have a fibrous morphology, and aerogel powders / particles can have a fibrous morphology. In addition, in certain embodiments, when the nanoporous carbon material contains additives (such as silicon or others), the inherent fibrous nanostructure of the carbon material is retained and acts as a bridge between the additive particles.

[0166] In the context of the present disclosure, the term "cycle life" refers to the number of complete charge / discharge cycles that an anode or battery (e.g., a LIB) can support before its capacity drops to less than about 80% of its original rated capacity. Cycle life can be affected by a variety of factors that are not significantly affected over time, such as the mechanical strength of the underlying substrate (e.g., carbon aerogel), the connectivity of the silicon particles within the aerogel, and the maintenance of the interconnectivity of the aerogel. It should be noted that it is a surprising aspect of certain embodiments of the present invention that these factors actually remain relatively unchanged over time. Cycle life can be determined by methods known in the art, such as, but not limited to, cycle testing, in which a battery cell is subjected to repeated charge / discharge cycles at a predetermined current rate and operating voltage. In the context of the present disclosure, unless otherwise stated, measurements of cycle life are obtained according to this method. In certain embodiments of the present disclosure, the cycle life of an energy storage device (such as a battery or an electrode thereof) is about 25 cycles or more, 50 cycles or more, 75 cycles or more, 100 cycles or more, 200 cycles or more, 300 cycles or more, 500 cycles or more, 1000 cycles or more, or in a range between any two of these values.

[0167] In the context of the present disclosure, the term "capacity" refers to the specific amount of energy or charge that a battery can store. Capacity is specifically measured as the discharge current that a battery can deliver over time per unit mass. It is usually recorded as ampere-hours or milliampere-hours per gram of total electrode mass, Ah / g or mAh / g. The capacity of a battery (especially an anode) can be determined by methods known in the art, such as, but not limited to: applying a fixed constant current load to a fully charged battery until the battery voltage reaches the discharge end voltage value; the time to reach the discharge end voltage multiplied by the constant current is the discharge capacity; by dividing the discharge capacity by the weight or volume of the electrode material, the specific capacity and volumetric capacity can be determined. In the context of the present disclosure, unless otherwise stated, the measured value of the capacity is obtained according to this method. In certain embodiments, the capacity of the aerogel material or composition of the present disclosure is about 200 mAh / g or more, 300 mAh / g or more, 400 mAh / g or more, 500 mAh / g or more, 600 mAh / g or more, 700 mAh / g or more, 800 mAh / g or more, 900 mAh / g or more, 1000 mAh / g or more, 1200 mAh / g or more, 1400 mAh / g or more, 1600 mAh / g or more, 1800 mAh / g or more, 2000 mAh / g or more, 2400 mAh / g or more, 2800 mAh / g or more, 3200 mAh / g or more, or in a range between any two of these values. Unless otherwise stated, when the nanoporous carbon material of the present disclosure is used in a battery, the capacity of the battery is reported at the 10th cycle.

[0168] In the context of the present disclosure, the term "silicon utilization" refers to the difference between the theoretical lithiation capacity of silicon and the measured capacity of the electrode based on the weight of silicon. Silicon utilization is specifically measured as the efficiency of silicon use within the electrode. It can be recorded as a percentage herein using the following equation:

[0169]

[0170] To calculate silicon utilization, the capacity of the electrode and the capacity of silicon are measured as discussed above. In certain embodiments, the silicon utilization of the aerogel material or composition of the present disclosure is about 20% or greater, 30% or greater, 40% or greater, 50% or greater, 60% or greater, 70% or greater, 80% or greater, 90% or greater, or in a range between any two of these values, where a higher percentage indicates better or more efficient silicon utilization. Unless otherwise stated, when the nanoporous carbon material of the present disclosure is used in a battery, the silicon utilization of the battery is reported at the 10th cycle.

[0171] In one embodiment, the present invention is an anode for a LIB comprising a silicon-doped, polyimide-derived carbon aerogel, wherein silicon particles are at least partially contained within the pores of the carbon aerogel. The general reactions and processes for developing polyimide-derived carbon aerogels (i.e., without silicon) are described in Figure 3 . It can be seen that the structure of the carbon aerogel pores can be adjusted to have different properties (e.g., pore volume, pore size distribution) according to the needs (e.g., the size or capacity of the electrode in the LIB). In another embodiment, the present invention is an electrode in a LIB or an electrochemical cell thereof comprising such an anode. In yet another embodiment, the present invention is a device or system that incorporates such an energy storage device. Examples include, but are not limited to, electric vehicles and electronic devices (e.g., mobile devices and drones).

[0172] In certain embodiments, the present invention is a method for forming or manufacturing a continuous porous carbon silicon composite material (such as a carbon aerogel). A polyimide precursor, such as a diamine and a dianhydride, each of which may include an aromatic group and / or an aliphatic group, is mixed in a suitable solvent (e.g., a polar aprotic solvent). Before adding an imidization gelling catalyst, silicon particles are mixed into a polyimide precursor in a solvent. An imidization gelling catalyst is then added to initiate gelation of the mixture. In an alternative embodiment, imidization can be accomplished by thermal imidization, wherein any suitable temperature and time range is considered (e.g., about 20 minutes to about 8 hours at about 100°C-200°C, followed by heating at about 300°C-400°C for about 20 minutes to about 1 hour). The gelled mixture is then dried to produce a continuous porous polyimide silicon composite material, wherein subcritical and / or supercritical carbon dioxide can be used for drying. Optionally, the polyimide silicon composite material can be compressed, preferably uniaxially compressed (e.g., up to 95% strain), to increase the density, which can be adjusted up to about 1.5 g / cc based on the amount of compression. In an example embodiment, the polyimide silicon composite material can be compressed to a strain greater than about 80% before pyrolyzing the composite material. Whether or not compression has been performed, the polyimide silicon composite material is pyrolyzed to produce a continuous porous carbon silicon composite material, wherein the resulting composite material contains greater than 0% and less than about 95% silicon by weight and contains a porosity of about 5%-99%. In certain embodiments, pyrolysis can be performed at a maximum temperature of about 750°C to about 1600°C, and graphitization can be performed optionally at about 1600°C to about 3000°C.

[0173] In certain embodiments, the carbon silicon composite material can be a monolithic structure or an independent structure, can be prepared on or outside a substrate, can be micronized into a powder form, or can be prepared as a granular material, such as a bead. In addition, the composite material can be reinforced with or without a nonwoven material or a woven material (such as fiber, foam, etc.). Optionally, the composite material can be pre-doped with a metal or metal oxide, such as, but not limited to, tin, sulfur, phosphorus, nickel, cobalt, manganese, lithium, magnesium, iron, zinc, boron, titanium, aluminum oxide, titanium oxide, niobium oxide, molybdenum oxide, silicon dioxide, and aluminosilicate. Further, the silicon particles can be pre-doped with a p-type acceptor (such as boron, aluminum, gallium, and indium) or an n-type donor (such as phosphorus, lithium, arsenic, antimony, bismuth).

[0174] In an alternative embodiment, the above method can be used to form or make a porous carbon-silicon composite material, except that instead of mixing silicon particles into a mixture of polyimide precursors in a solvent, a silicate (e.g., silicon dioxide, aluminosilicate and / or halloysite) and a reducing agent (e.g., magnesium, lithium, sodium, potassium, aluminum, calcium, or a combination thereof) are mixed into a mixture of polyimide precursors in a solvent. After drying, a continuous porous polyimide silicate and reducing agent composite material is formed, which can be optionally compressed to adjust the density. In this case (i.e., when a silicate and a reducing agent are used), the silicate and reducing agent react with hydrogen under inert conditions at a temperature above about 700° C. to form silicon in situ in the carbon composite material.

[0175] In a further alternative embodiment, the above method can be used, except that instead of adding silicon or silicate + reducing agent to the polyimide precursor, a continuous porous carbon can be formed first (i.e., the polyimide precursor is imidized, dried and pyrolyzed using a catalyst or heating), and then silicon is deposited on or in the porous carbon. In this case, silicon is deposited by dipping the porous carbon into a silicon-forming silane precursor, then heating under inert conditions to decompose the silane, forming a conformal silicon coating in the porous carbon. This dipping process can be performed multiple times to increase the thickness and increase the silicon content to about 95% by weight. In other embodiments, silicon can be deposited by atomic layer deposition or CVD.

[0176] Additionally, it is contemplated herein that the pore size can be adjusted as desired. Five main methods of adjusting the pore size are taught herein. First, the amount of solid content, specifically the amount of polyimide precursor monomers (e.g., aromatic or aliphatic diamines and aromatic or aliphatic dianhydrides), can adjust the pore size. Smaller pore sizes are due to a larger amount of solids per unit volume of fluid, which allows for tighter interconnections because there is less available space. It should be noted that no matter how much solids are used, there is no measurable change in the pillar width. The amount of solids has more to do with how dense the network is.

[0177] Another method of adjusting the pore size is to use radiation (e.g., radio waves, microwaves, infrared, visible light, ultraviolet light, X-rays, gamma rays) on the polyimide or carbon composite. Radiation has an oxidizing effect, resulting in an increase in surface area, an increase in pore size, and a broadening of the pore size distribution. Third, the pore size is affected by macroscopic compression of the polyimide composite. As demonstrated in the following examples, the pore size decreases with compression.

[0178] Another method of adjusting the pore size is ion bombardment of polyimide or carbon composites. The effect of ion bombardment depends on the specific method. For example, there is additive ion bombardment (such as CVD), where something is added, resulting in a decrease in pore size. There is also destructive ion bombardment, where the pore size increases. Finally, the pore size can be adjusted (increased or decreased) by thermal treatment in different gas environments (such as the presence of carbon dioxide or carbon monoxide), chemically active environments, hydrogen reduction environments, etc. For example, a carbon dioxide environment is known to produce activated carbon, where, in the case of activation, substances are removed, the pore size increases, and the surface area increases.

[0179] While each of the above methods of adjusting pore size are contemplated, the present disclosure will focus more on varying the solid content (polyimide precursor) and compression of the polyimide composite prior to carbonization.

[0180] Example

[0181] The following examples are described for illustrative purposes only and are not intended to limit the scope of the various embodiments of the present invention in any way.

[0182] Example 1: CPI composite material with low doping level

[0183] A. CPI with 9% dopant dispersed in polyimide

[0184] PI gel was prepared from 1:1 molar ratio of pyromellitic dianhydride (PMDA) and 1,4-phenylenediamine (PDA) in DMAC solvent, with a target density of 0.06 g / cc. The precursors were mixed at room temperature for 3 hours, then acetic anhydride (AA) was added to PMDA in a 4.3 molar ratio, and mixed with the solution for 2 hours. Powder dopants, such as graphite CNGT0112 with a thickness of about 40 nm and a length of about 400-600 nm and silicon BASIC005 with a spherical particle diameter of about 30 nm were obtained from ACS MATERIALS. Graphite or silicon (Si) was doped in the solution, accounting for 4.5% of the total solids. Graphite was mixed with the solution for 10 minutes with a magnetic bar, and the mixture and imidization of the doped mixture were catalyzed with pyridine (Py). According to visual evaluation, graphite was well dispersed. After stirring the silicon with the polyimide solution for 10 minutes, the visual dispersibility was poor (i.e., sedimentation and / or particle aggregation in the solution state was proved) and the mixture was further ultrasonicated for 3 minutes. Once the dispersion quality was improved, pyridine catalyst was added to the mixture. The molar ratio of Py to PMDA was 4.0.

[0185] To prepare the PI composites, the solution was cast between glass plates with spacers at the edges to control the thickness. Other suitable methods of casting the solution are also considered herein. The spacers were made of 200 micron thick aluminum foil. Monoliths of approximately 2 inches in diameter were also cast in Teflon containers. The gelation time at ambient temperature was approximately 11.5 minutes for the graphite-doped samples and approximately 15.5 minutes for the silicon-doped samples. The gel was cured overnight at room temperature and then ethanol exchanged 3 times at 68°C before supercritical CO2 extraction. The PI aerogel composites were compressed from approximately 250 microns to various thicknesses and carbonized by pyrolysis at 1050°C for 2 hours under an inert atmosphere to form CPI composites. The % dopant in CPI was calculated to be approximately 9% based on the amount of dopant in the formulation and the weight of the composite retained after pyrolysis.

[0186] The density of the compressed CPI composites with a thickness of about 80-50 microns ranged from about 0.24-0.36 g / cc (Tables 1 and Figure 4 ).

[0187]

[0188] Table 1. Properties of low density CPI composites doped with 9% graphite or Si.

[0189] The porosity was calculated based on the actual density and skeletal density of the CPI composites. Since the density of amorphous carbon ranges from about 2.0-2.3 g / cc, and the density of silicon or graphite is about 2.3 g / cc, the skeletal density used in these calculations for all composites was about 2.2 g / cc. These low density composites were calculated to have high porosity of 84-89%.

[0190] B. Dispersed in solvent by mixing, CPI with 9% dopant

[0191] Similar experiments were conducted using a solution of 0.10 g / cc polyimide target density. In this case, the dopant was mixed with a portion of DMAC for 10 minutes and added to the mixture before catalysis. A 500 micron thick Teflon gasket was used for casting. The molar ratio of Py to PMDA was 2.0. The gelation time for the graphite-doped sample was about 2.5 minutes, and the time for the silicon-doped sample was about 4.0 minutes. The gel was extracted using supercritical CO2. The PI aerogel composites were compressed from about 580 microns to various thicknesses and carbonized by pyrolysis at 1050°C for 2 hours to form CPI composites.

[0192] The properties of the CPI composites are shown in Table 2. As expected, the more compressed composites showed slightly lower porosity.

[0193]

[0194] Table 2. Properties of high density CPI composites doped with 9% Graphite or Si.

[0195] The density of the compressed CPI composites (approximately 115-80 micron thickness) ranged from approximately 0.57-0.87 g / cc. The density of the silicon-doped CPI composites was slightly lower ( Figure 5 ).

[0196] The density and shrinkage of the doped PI aerogel monoliths after pyrolysis are shown in Table 3. The density of the uncompressed monoliths (LS1 & LG1) is lower compared to the compressed composites (LS2 & LG2).

[0197]

[0198] Table 3. Density and shrinkage of doped CPI aerogels as a whole.

[0199] Figure 6A-6B SEM images of pyrolyzed composites doped with silicon are shown; note that Figure 6B The fibrous morphology of the silicon-doped CPI composite is shown. Pockets of silicon agglomerates and silicon nanowires are embedded in the carbon matrix. The anode discharge capacity for each dopant content in half-cell battery tests is shown in Figure 2. Figure 7 As shown. Silicon provides significantly higher initial capacity compared to graphite dopants. Although the initial capacity decreases with cycling, its reversible capacity is still significantly higher than that of graphite alone in conventional anodes. In addition, the capacity fade may be caused by the foil electrode used in these half-cell battery tests, which cannot operate at the high capacity of silicon-containing electrodes.

[0200] Example 2: CPI composite material with high PI solid content and high silicon doping level

[0201] A. CPI doped with 27% silicon by ultrasonic dispersion in solvent

[0202] PI gel was prepared using a 0.10 g / cc target density. PMDA and PDA precursors were mixed at room temperature for 3 hours. Silicon powder of 30 nm particle size was ultrasonicated in DMAC solvent for 20 seconds alone and added to the mixture at a total solid content of 15.0% and stirred for 15 minutes. AA was added to the doped mixture at a 4.3 molar ratio relative to PMDA and mixed for 2 hours. Pyridine was used to catalyze the mixture at a 2.0 molar ratio relative to PMDA. The composite was cast between glass plates using a 500 micron thick Teflon gasket. A 2 inch diameter monolith was also cast in a Teflon container. The gelation time at ambient temperature was about 3.5 minutes. The gel was cured overnight at room temperature and then three (3) ethanol exchanges were performed at 68°C before supercritical CO2 extraction. The PI aerogel composite was compressed and carbonized at 1050°C for 2 hours to form a CPI composite.

[0203] B. CPI doped with 46% and 64% silicon by ultrasonic dispersion in solvent

[0204] PI gel was prepared with a target density of 0.08 g / cc. PMDA and PDA precursors were mixed at room temperature for 4 hours. AA was then added and the solution was mixed for 2 hours. Silicon powder with a particle size of 30 nm was ultrasonicated in a DMAC solvent for 1 minute and added to the mixture 5 minutes before the addition of the pyridine catalyst. Silicon was added in an amount of about 29.7% and about 49.6% of each total solid. A mixture of Py and PMDA catalytic doping in a 3.2 molar ratio was used. Composite materials were cast using a 500 micron thick gasket. The gelation time at ambient temperature was about 6.5 minutes. After processing and extraction, the PI aerogel composite was compressed and pyrolyzed at 1050°C for 2 hours for carbonization to form a CPI composite.

[0205] Table 4 and Figure 8 A comparison of the surface area and porosity of pyrolyzed, non-compressed monoliths doped with different amounts of silicon is given in . As the silicon content in the CPI increases, the surface area, micropore area, and pore volume decrease.

[0206]

[0207] Table 4. Density and porosity of CPI monoliths doped with different amounts of Si. In addition, it can be seen that the pore volume is at least about 1.5 cc / g.

[0208] The pore size distribution at the maximum peak depends on the silicon content and the dispersion of silicon ( Fig. 9). In general, by increasing the silicon content, the pore size at the maximum peak of the distribution shifts from about 23 nm to about 26 nm to about 34 nm as the Si content increases from about 9% to about 46% to about 64%, respectively. The basic pore size distribution also broadens with increasing silicon content.

[0209] However, comparing the Td 0.10 g / cc samples, the 27% Si bulk prepared by adding silicon before AA and mixing with the solution for a long time shows a shift in the main peak to about 15 nm pore size, while the 9% Si bulk prepared by mixing with the solution for a short time shows a shift in the main peak to about 23 nm. The sample doped with 27% Si shows a bimodal pore size distribution with another small broad band centered at 30 nm. This is likely due to incomplete dispersion of silicon in the high target density, high viscosity mixture. This is also the case with the higher silicon content (64%) sample in the series, which also shows a bimodal pore size distribution.

[0210] The compressed, pyrolyzed composite material had higher density, lower surface area and pore volume compared to the uncompressed monolithic material (Table 5). Density was calculated as the average of six (6) samples.

[0211]

[0212] Table 5. Density and porosity of CPI compression composites with variable Si doping. Additionally, it can be seen that the volume is at least about 0.3 cc / g.

[0213] Half-cells (2032-button cells) were fabricated with CPI composites as electrodes, lithium foil as counter electrode and CELGARD 2500 as microporous separator between electrodes. The electrolyte was 1.0M LiPF6 in EC:EMC (3:7 by weight). Unless otherwise stated, all cells were tested using an ARBIN BT2043 tester and a charge / discharge rate of 0.1C. Table 6 gives the discharge capacity of the compressed CPI composites at the 5th cycle.

[0214]

[0215] Table 6. Discharge capacity of Si-doped compressed CPI composites (half-cell test).

[0216] The best performance of these samples was obtained at Si contents of 30–50% based on CPI, as Fig.10 shown.

[0217] Figures 11A-11CSEM images of composites doped with high Si content are given, which also show the fibrous morphology of the composites. The silicon (lighter areas) is more compact in the samples with higher doping levels. Si nanowires can be observed in all samples at high magnification. It can be seen that the silicon has direct contact and interpenetration with the carbon porous structure (darker areas).

[0218] Figures 12A-12F The cycling capacity based on Si and electrode content is shown, with the raw data in Table 7. Increasing Si loading of the CPI composites results in a faster capacity drop with cycling. As such, the capacity fade may be due to the foil electrode used in these half-cell battery tests, which is unable to operate at the high capacities of the silicon-containing electrodes.

[0219]

[0220] Table 7. Data comparing the discharge capacity of silicon (different concentrations) and whole electrodes.

[0221] As can be seen from Table 7, the silicon utilization can be calculated to be about 20% to about 90%, depending on the amount of silicon incorporated into the electrode, or even more optimally about 50% to about 90%. Narrower ranges are also contemplated herein based on the desired benefits of the final composite material (e.g., the amount of silicon required). Overall, this wider range is significantly higher than the range seen in conventional technology. Furthermore, it can be seen that the capacity at the 10th cycle varies depending on the silicon concentration, but can advantageously be about 800 mAh / g or more.

[0222] Example 3: Silicon-doped CPI composite material with low PI solid content

[0223] A. CPI doped with 66% silicon dispersed in a solvent by ultrasound

[0224] PI gel was prepared with a target density of 0.05 g / cc. PMDA and PDA precursors were mixed at room temperature for 3 hours. AA was then added and mixed with the solution for 2 hours. Silicon powder of about 30 nm particle size was ultrasonicated in DMAC solvent for 2 minutes separately and added to the mixture 30 minutes before adding the pyridine catalyst. Silicon was added at about 60.5% of the total solids. The Py / PMDA molar ratio was 7.5. The gelation time at ambient temperature was about 5.5 minutes. The composite material was cast using a 500 micron thick gasket. After processing and extraction, the PI gel composite was compressed and carbonized at 1050°C for 2 hours to form a CPI composite material. The Si content based on CPI was 66%.

[0225] The CPI composites compressed to different thicknesses were examined by SEM, e.g. Figures 16A-16B, which depicts the fibrous morphology of the CPI composite. No silicon nanowires were observed in these images. Table 8 shows the properties of the less compressed (LC) and more compressed (MC) composites tested in half-cell cells.

[0226] ID Thickness(μm) Density(g / cc) Weight(g) Length (diameter) (cm) Width (cm) LC 323 0.366 0.0202 1.340 1.275 MC 170 0.628 0.0194 1.431 1.269

[0227] Table 8. Properties of CPI composites doped with 66% Si.

[0228] Figures 14A-14B The effect of thickness on anode performance is demonstrated. By reducing the thickness by about half, the electrode capacity is essentially doubled, and the 170 micron thick electrode shows a discharge capacity of over 1500 mAh / g after the 4th cycle. Although these high capacity CPI composites with high amounts of silicon loading (66%) are unstable after multiple cycles, the capacity fade is likely due to the foil electrode used in these half-cell battery tests, which prevents the electrode from operating at the high capacities of the silicon-containing electrodes.

[0229] B. CPI doped with 45% silicon dispersed by mixing in solvent with or without dispersant

[0230] PI gels were prepared with a target density of 0.05 g / cc. PMDA and PDA precursors were mixed at room temperature for 17 hours. AA was then added and mixed with the solution for 3 hours. Separately, silicon powder with a particle size of 30 nm was mixed in a DMAC solvent with or without a dispersant for 20 hours. A control C45 sample was prepared in the absence of a dispersant. BYK384 was used as a dispersant in sample B45 at 20% by weight based on the weight of Si. Pluronic F87 was used as a nonionic surfactant in sample P45 at 20% by weight based on the weight of Si. The dispersion was added to the mixture 30 minutes before the addition of the pyridine catalyst. 27.3% silicon was added to the total solids. The Py / PMDA molar ratio was 7.0. The gelation time at ambient temperature was about 11 minutes. Composites were cast using a 500 micron thick gasket. After processing and extraction, the PI aerogel composite was compressed and carbonized at 1050°C for 2 hours to form a CPI composite. The Si content based on CPI was about 45%.

[0231] Figures 15A-15B Figure 2 shows the SEM images of the compressed C45 polyimide composite before and after pyrolysis. Fig. 15B The fibrous morphology of the CPI composite is also shown. The Si nanowires are not visible in the non-pyrolyzed composite, only in the CPI. Figures 16A-16CSEM images of CPI composites with and without dispersant are shown in . The properties of the CPI composites submitted for battery testing are shown in Table 9. The conductivity obtained for these samples was about 26-27 S / cm.

[0232] ID Thickness(μm) Density(g / cc) Electrical conductivity (S / cm) Silicon utilization at the 10th cycle C45 75 0.597 27.0±0.2 - B45 95 0.584 26.8±1.0 69.66% P45 90 0.512 26.0±7.1 78.71%

[0233] Table 9. CPI composites prepared with and without dispersants for battery testing.

[0234] The half-cell battery test results show that the P45 composite material has higher discharge capacity and lower irreversible capacity loss ( Figures 17A-17C ). Alternatively, capacity fade may be due to the foil electrodes used in these half-cell battery tests, which prevented the electrodes from operating at the high capacities of silicon-containing electrodes.

[0235] The composites of the P45 formulation were cast at three (3) thicknesses: 780, 580, and 370 microns. Each of these PI batches was cut into approximately 0.5 x 0.5 square inch composite sheets, compressed at three (3) different levels using a hydraulic press, and then pyrolyzed. Table 10 and Fig.18 The results are shown in .

[0236] Initial PI thickness (μm) Final CPI thickness (μm) CPI composite density (g / cc) Porosity (%) 780 70 0.960 56.4 780 100 0.625 71.6 780 115 0.596 72.9 580 70 0.740 66.4 580 80 0.660 70.0 580 120 0.479 78.2 370 50 0.664 69.8 370 100 0.400 81.8 370 130 0.315 85.7

[0237] Table 10. Properties of P45 CPI composites at different levels of compression.

[0238] The density of Si-doped CPI composites varies between 0.3 and 1.0 g / cc at thicknesses between about 50-130 microns ( Fig.18 ). The density increases with the initial thickness of the PI composite. The porosity ranges from about 50-90%.

[0239] Electrical conductivity of silicon-doped CPI composites. The electrical conductivity of CPI composites doped with various silicon levels pyrolyzed at 1050°C was measured using a Keithley 4-point probe apparatus. The conductivity of the samples varied from about 5-80 S / cm (Table 11). The conductivity of the undoped carbon composite was about 13.6 S / cm, which is within the expected range for amorphous carbon known in the art. Although the conductivity of silicon is reported to be 1.6 x 10 -5S / cm, but the conductivity of silicon nanowires can be three (3) orders of magnitude higher (0.03 S / cm) (Sabar D. Hutagalung, Mohammed M. Fadhali, Raed A. Areshi and Fui D. Tan, Optical and Electrical Characteristics of Silicon Nanowires Prepared by Electroless Etching, Nanoscale Research Letters, 2017, 12: 425).

[0240] Si% based on CPI Target density (g / cc) Density(g / cc) Electrical conductivity (S / cm) 0 0.075 0.310 13.6 9 0.100 0.680 56.8 27 0.100 0.862 78.1 45 0.050 0.525 26.9 64 0.080 0.550 15.9 66 0.050 0.712 5.5

[0241] Table 11. Density and conductivity of CPI composites with different Si concentrations.

[0242] Generally, conductivity increases with density. However, when silicon concentration exceeds 60%, conductivity is lower than expected ( Fig.19 ). At such high silicon contents, the connectivity of the carbon network is disrupted, resulting in reduced conductivity. The sample doped with 27% wt Si based on CPI showed the highest conductivity, indicating the best dispersion of silicon for the purpose of high conductivity. It can be seen that the wider optimal range is about 5% to about 80% wt Si based on CPI, or more specifically about 5% to 50% wt Si based on CPI. It can be seen in Tables 9 and 11 that varying the silicon content can adjust the conductivity to up to about 80 S / cm. Therefore, it can be expected that the conductivity can be higher than about 5 S / cm, 10 S / cm, 15 S / cm, 25 S / cm, 50 S / cm and 75 S / cm, where a wider range and more precise conductivity can be adjusted based on the silicon content.

[0243] Example 4: Carbonized polyimide aerogel with high pore volume and narrow pore size distribution

[0244] PI gel was prepared by reacting 6 g PMDA with 3 g PDA in 100 mL DMAC at room temperature for 2-24 hours to form polyamic acid. Subsequently, 8.86 g AA was added to the polyamic acid solution as a chemical imidization agent (see Fig. 20). The acidified polyamide solution is vigorously mixed for at least 2 hours. The resulting mixture is diluted with DMAC to the target density of the desired PI aerogel. 1-4g Py per 100mL mixture is added to the final solution to promote gelation, which occurs within 4-25 minutes. Before gelation, the mixture is cast into a desired form (e.g., film, monolith, reinforcing fiber, etc.). The obtained gel is then aged in an oven at 65-70°C and washed / rinsed with ethanol several times before supercritical drying. In an inert environment (nitrogen flow), the PI aerogel is converted into a carbon aerogel by pyrolyzing it at 1050°C for 2 hours. Without being bound by theory, the physical and structural properties of the carbonized PI aerogel depend on the precursor mixing time and the amount of Py.

[0245] Table 12 reports the structural properties of the four CPI aerogels tested by the nitrogen adsorption-desorption technique. The four samples vary in mixing time and Py amount. The target density was fixed at 0.05 g / cc. Interestingly, all samples exhibit relatively similar surface BET, but the pore size distribution and pore volume appear to be affected by the synthesis parameters.

[0246]

[0247] 1: Mixing time of the two precursors.

[0248] 2: Amount of pyridine added for gelation (g / 100mL solution)

[0249] Table 12. Physical and structural properties of different CPI aerogels.

[0250] Example 5: Carbonized polyimide aerogel loaded with Si

[0251] Silicon particles (30nm) of different concentrations are joined in the polyamic acid solution.The synthesis of solution is identical with that described in Example 4.However, in this composite material system (PI / Si), before silicon particles are mixed with polyamic acid solution, first silicon particles are dispersed in DMAC for at least 2 hours.For avoiding Si sedimentation, the gel time of silicon / polyamic acid solution keeps relatively short (4-6 minute).For this reason, 4g pyridine / 100mL mixture is used to meet the target gel time.Before gelation, the mixture is cast into required form (for example film, integral or reinforcing fiber etc.).Then the gel obtained is aged at 65-70 ℃ in a baking oven and washed with alcohol / rinsed several times before supercritical drying.

[0252] A. 22-25wt% Silicon in Polyimide Carbon Aerogel Composites

[0253] During the polymerization step, the target density of the composite was fixed at 0.06 g / cc, and the Si loading was about 11.88 wt%. The silicon content was adjusted after pyrolysis of the polyimide aerogel at 1050 °C for 2 h, since the weight loss of all samples was not less than 50%. Four composites with different thicknesses were produced:

[0254] MT (medium-thick composite material about 0.3-0.4mm)

[0255] T (thick composite material about 0.6-0.8mm)

[0256] MTC (medium-thickness compression composite material about 0.07-0.09mm)

[0257] TC (thick compressed composite material about 0.12-0.16mm)

[0258] Different PI / Si samples were pyrolyzed at 1050°C for 2 hours and the cells were tested. The physical properties of the samples are listed in Table 13.

[0259]

[0260]

[0261] Table 13. Physical properties of different C / Si composites.

[0262] Fig.23 An SEM image of the pyrolyzed composite material (MT material) doped with about 25% Si can be seen in. The SEM image shows at high magnification some agglomeration of Si and silicon nanowires embedded in the carbon matrix.

[0263] Figures 25A-25B The cycling capacity of MTC5 and MT5 samples based on Si and electrode content is shown. MTC5 (compressed CPI aerogel) has been up to 400 cycles and MT5 (non-compressed CPI aerogel) has been up to 150 cycles. The two samples show different behaviors. MTC5 shows a relatively stable capacity discharge up to 200 cycles, followed by a capacity drop, which may be due to the foil electrode in the half-cell battery test, as discussed above.

[0264] B. 39wt% Silicon in Polyimide Carbon Aerogel Composites

[0265] In the next round of synthesis, the Si content was increased to 39 wt %, expected to reduce the capacity loss during the first discharge. The polyimide gel was prepared with a target density of 0.05 g / cc. The polyamic acid solution was prepared by mixing PMDA and PDA in DMAC for more than 16 hours. Separately, silicon powder was dispersed in DMAC for 2 hours and then added to the polyamic acid solution before adding pyridine. After adding pyridine, a composite was prepared between Teflon plates using 500 micron spacers. The aerogel composite was compressed and then pyrolyzed at 1050°C for 2 hours. The silicon content was 39 wt % of the total solids.

[0266] The properties of the compressed (PISi1NC(C)) and uncompressed (PISi7NC) composites tested in half-cell batteries are shown in Table 14.

[0267]

[0268] Table 14. Physical properties of C / Si (Si about 39 wt%) composites

[0269] Figures 26A-26B The discharge capacity is shown as a function of cycling for anodes made with the two materials reported in Table 14. When the silicon content is increased from 25 wt% (previous materials, i.e., MT5 and MTC5) to 39 wt%, the anode-based discharge capacity increases significantly.

[0270] Example 6: Fiber-reinforced C / Si aerogel

[0271] The samples with different surface densities (2, 4 and 10 g / m 2 ) were used as reinforcements for C / Si aerogels. The synthesis and processing of PI / Si aerogels were the same as described previously, with one exception. During the gelation step, the mixture was cast into fibers. After supercritical drying, the carbon fiber-reinforced PI / Si composites were cut into 15 mm (inner diameter (ID)) round samples using a dye cutter and pyrolyzed at 1050 °C for 2 h. Figure 27-29 The properties and micrographs of carbonized PI / Si / carbon fiber samples are shown.

[0272] After pyrolysis, 2- and 4-g / m 2 The carbon fiber reinforced samples experienced high shrinkage of both the carbon aerogel and the reinforcement. Figure 28-29 The high voids show that these two materials are not particularly suitable for battery testing. Fig. 27 Medium, use 10-g / m 2Carbon fiber reinforced C / Si showed better microstructure and no signs of voids. However, the Si content was low (about 21%) and the fiber density was high (>30wt%). This composite was tested for charge and discharge capacity in such a system. Fig.30 Reported in Fig. 27 Cycling capacity of samples shown (based on Si and electrode content).

[0273] In another embodiment, cellulose fibers were also tested as reinforcement for C / Si. The synthesis route was the same as that used for carbon fibers. Cellulose fibers accounted for 68% (by weight) of the C / Si composite, although most of the fiber decomposed after pyrolysis, as the %Si increased from 6% to 24% after pyrolysis.

[0274] The physical properties of C / Si reinforced with cellulose fibers are reported in Table 15.

[0275]

[0276] Table 15. Physical properties and composition of C / Si reinforced with cellulose fibers.

[0277] Fig.31 The cycling capacity for cellulose fiber reinforced C / Si based on Si and electrode content was reported in. The performance of this material is similar to that of C / Si reinforced with carbon fibers.

[0278] Example 7: Improved silicon dispersion in PI aerogel

[0279] PI composites and monolithic gels with 47% silicon loading and a target density of 0.05g / cc were prepared. A route to better disperse silicon in the polyimide matrix to avoid aggregation was carried out. Starting from solution synthesis, silicon was dispersed and mixed with PMDA and PDA. The polyamic acid solution + silicon was mixed for 16 hours. Acetic acid was added and mixed with the solution for 4 hours. Rapid gelation (about 4 minutes) was ensured by adding an appropriate amount of Py to the acidified polyimide / silicon mixture. Composites with a thickness of about 200-300 microns were cast, as well as thick monoliths. After supercritical drying, the PI / Si aerogel composites were compressed and then pyrolyzed at 1050°C for 2 hours.

[0280] Subsequently, a number of different samples (eg, compressed, uncompressed, monolithic, etc.) were analyzed by SEM to evaluate the dispersion of silicon in the carbon matrix. Fig.32 Three cross-sectional SEM images of a thick uncompressed composite (0.60 mm) are shown. At low magnification (left), uniform and well-distributed silicon is shown. Large silicon clusters are also shown. At higher magnification (right), it can be seen that the high density of silicon is well embedded in the carbon matrix. Fig.33Three cross-sectional SEM images of the thin composite (0.12 mm) are shown. The same observations were made, namely good Si dispersion and proper impregnation into the carbon matrix. The overall cross-sectional SEM image ( Fig.34 ) clearly confirms the same structure shown in thick and thin composites.

[0281] Figure 35-36 A side-by-side comparison of two differently processed C / Si composites is shown. On the left (in both images) are monoliths and composites cast from Si / PAA solutions mixed for 16 hours (long contact). On the right are monoliths and composites made from Si / PAA solutions mixed for 4-6 minutes (short contact). Different Si distributions are observed in the two processes. Long contact ensures better Si dispersion than short contact.

[0282] Half-cell tests were performed on compressed and uncompressed C / Si composites. Both samples, PISi3 (uncompressed) and PISi6C (compressed), have good dispersion of Si in the carbon aerogel matrix. Table 16 reports the physical properties of the two samples.

[0283]

[0284] Table 16. Physical properties of C / Si (mixed for 16 hours) submitted for half-cell testing.

[0285] Figure 37-38 The charge-discharge cycles of the two samples are shown in . The samples performed surprisingly well, with the compressed sample (PISi6C) showing stable cycling performance.

[0286] Example 8: Fabrication of C / Si circular electrode

[0287] In the previous embodiment, the C / Si electrode is square (about 1 cm 2 ) form, and test the battery performance in a round cell (ID = 15mm). In order to obtain higher efficiency and more reliable test results, it is necessary to test the round C / Si electrode. Therefore, a die-cutting machine is used to perform the route of making round electrodes.

[0288] A PI aerogel composite with a target density of 0.13 g / cc and 31.4% Si (using 16 hours of mixing) was prepared. After extraction, the density of the final aerogel was measured to be about 0.213 g / cc. Using a die cutter, multiple round aerogel composites with an ID of 15 mm were produced (see Fig.39 ). The thickness of the sample is about 0.43 mm. Part of the sample was compressed and then pyrolyzed at 1050℃ for 2 hours. The characteristics of the pyrolyzed circular electrode are as follows:

[0289] Weightlessness: about 41%

[0290] Uncompressed sample: about 0.261 g / cc (1.1 cm ID, 0.38 mm thick)

[0291] Compressed sample: about 0.652g / cc (1.35cm ID, 0.11mm thickness)

[0292] Figure 40-41 Compressed and uncompressed half-cell performance is shown. The capacity of the uncompressed sample appears to be higher than the compressed sample, although the uncompressed sample also produces a more erratic capacity.

[0293] Example 9. Carbonized PF aerogel loaded with Si

[0294] Carbon aerogels made of PF are also considered in this article for the manufacture of C / Si aerogel electrodes. For PF systems, high target density (>0.7g / cc) aerogels can be achieved through synthetic routes. The obtained aerogels do not need to be compressed. The obtained aerogels do not need to be compressed. High-density PF gel composites are prepared as follows. 22g of phloroglucinol was dissolved in 100mL of ethanol, and 44mL of 2-furfural was added to the phloroglucinol solution. The resulting solution was mixed for 30 minutes. 5wt% of silicon was added to the mixture and mixed vigorously for another 30 minutes. The PF mixture can be gelled by alkali (diamine or triamine), and the gelation time is about 20-40 minutes, depending on the concentration of the alkali. In this case and if silicon is present, the gelation time should be shorter (less than 1 minute) to avoid any silicon precipitation during the gelation process. Chloric acid (HCl) is used to catalyze the gelation of PF, and the gelation time is as short as 20 seconds. Therefore, 0.012 g of concentrated HCl per 100 mL of the mixture was added to the mixture, mixed for 20 seconds and cast between Teflon plates to prepare the gel. After aging and solvent exchange, the PF gel composite was dried with supercritical CO2. The obtained PF / Si aerogel had the following properties:

[0295] Two thicknesses of composite materials: about 0.2mm and about 0.1mm

[0296] Final density of aerogel: about 0.7g / cc

[0297] Afterwards, pyrolysis was carried out at 1050°C for 2 hours under inert gas to obtain a C / Si aerogel with a density of 0.77 g / cc and an adjusted %Si of 10 wt%. 2 )(See Fig.42 ).

[0298] Through liquid nitrogen adsorption-desorption test, C / Si aerogel has 541m 2 / g and a pore volume of 0.32cc / g. Interestingly, the micropore area accounts for 80% of the total surface area, which confirms the dense structure shown in the SEM images (see Fig.43 ). In addition, the carbon aerogel composite samples containing Si (where the carbon comes from PF) resulted in high capacity loss after the first cycle and very low total capacity (see Fig.44 ). These results highlight the unique properties of Si that can be better expressed in fibrous morphologies, such as those seen in polyimide-derived nanoporous carbon / carbon aerogels.

[0299] Example 10: Nanoindentation as a measure of mechanical strength

[0300] Multiple CPI composite samples were prepared using the above method, where variables in the samples included silicon content and density. Young's modulus of each sample was measured using nanoindentation, which tests the hardness of the material. More specifically, twenty (20) indentations were run on the sample surface. About 8-10 indentations were selected to obtain average data and standard deviations for each mechanical property.

[0301] The indentation locations were selected under the microscope where the surface was relatively clean and smooth and with few surface features to provide more reliable data. A maximum load of 50-mN was selected for samples 1 and 2 because they were softer than the other samples. Samples 3-7 used a 300-mN indentation load. Table 18 shows the results and other properties. Fig.45 plots the modulus versus density, and Fig.46 The relationship between modulus and density is plotted.

[0302] # %Si / (C+Si) %Si / (PI+Si) Td(g / cc) Density(g / cc) Young's modulus (Gpa) 1 66 60.5 0.05 0.644 0.279±0.022 2 66 60.5 0.05 0.608 0.504±0.038 3 45 27.3 0.05 0.605 4.049±0.317 4 45 27.3 0.05 0.480 2.911±0.428 5 64 49.6 0.08 0.739 1.735±0.173 6 64 49.6 0.08 0.658 3.381±0.168 7 45 27.3 0.05 0.771 8.218±0.657 8 45 27.3 0.05 0.306 0.883±0.053

[0303] Table 18. Physical properties of CPI samples tested using nanoindentation method.

[0304] Example 11: CPI beads doped with 45% silicon

[0305] PI gel beads were prepared with a target density of 0.10 g / cc. PMDA and PDA precursors were mixed in DMAC solvent at room temperature for 3 hours. AA was then added and mixed with the solution for 2 hours. Separately, 30 nm particle size silicon powder was ultrasonicated in DMAC solvent for 1 minute and added to the mixture 5 minutes before the addition of pyridine catalyst. Silicon was added at about 24% of the total solids. A mixture of Py and PMDA catalytic doping was used at a 3.2 molar ratio. Before gelation, the catalyzed sol containing silicon particles was poured into a stirred container with silicone oil as the dispersion medium (the volume ratio of silicone oil: catalyzed sol was 10:1). The gelled PI beads were separated from the silicone oil by filtration, then rinsed with ethanol, and then dried by supercritical CO2 extraction. The PI aerogel-silicon composite beads were then pyrolyzed at 1050°C for 2 hours to form CPI silicon composite beads with a tap density of 0.7 g / cc and D50=15 μm.

[0306] Example 12: Electrodes prepared from CPI beads

[0307] The anode electrode was prepared using the CPI silicon composite beads prepared according to Example 11 on a Cu foil as a current collector using a slurry containing 80 wt% CPI silicon composite beads, 10 wt% polyacrylic acid (PAA) binder and 10 wt% hard carbon conductive additive (C65), mixed in water at a total solid content of about 36 wt%. The slurry was cast onto the Cu foil using a doctor blade. After drying and calendering, a loading of 3.1 mg / cm 2 And an electrode with a density of 0.7g / cc.

[0308] Example 13: Half-cell constructed from CPI electrodes

[0309] A half-cell (2032 button cell) was constructed with the CPI composite electrode prepared according to Example 12, using lithium foil as the counter electrode and CELGARD 2500 as the microporous separator between the electrodes. The electrolyte was 1.0M LiPF6 in ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (3:7 weight ratio) and 5% fluoroethylene carbonate (FEC). All cells were tested using an ARBIN BT2043 tester. The protocol for testing the cells included 4 cycles with a charge / discharge rate of C / 20. Subsequent cycles were performed at different rates between C / 20 and 5C. Fig.48 The half-cell cycling performance of a CPI composite electrode containing 30 wt% silicon particles is shown. The electrode was prepared from a slurry containing 80 wt% CPI silicon composite beads, 10 wt% polyamic acid (PAA) binder and 10 wt% hard carbon conductive additive (C65). Fig.48The graph shows the relationship between the discharge capacity (mAh / g, based on the total weight of the electrode) and coulombic efficiency and the number of cycles in 1.0 M LiPF6 in ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (3:7 weight ratio) and 5 wt% fluoroethylene carbonate (FEC).

[0310] Example 14: Alternative method for producing PI aerogels

[0311] The previous embodiments discussed herein teach certain methods of forming PI aerogels. In certain embodiments, the present invention also contemplates alternative methods of forming PI aerogels. A set of non-exhaustive and non-limiting examples of such alternative methods will now be discussed.

[0312] For example, U.S. Patent No. 6,399,669 to Suzuki et al. teaches four (4) related methods for preparing PI dry gels (aerogels). In the first method, a PI precursor is synthesized and then an imide is formed from the PI precursor to produce a polyimide. A PI solution or a swollen mass is prepared, and the solution / swollen mass is gelled to produce a PI wet gel. This wet gel is dried to produce a PI dry gel (aerogel). In the second method, a PI precursor is synthesized and then a PI precursor solution or a swollen mass is prepared. The solution / swollen mass is gelled to produce a PI precursor wet gel. An imide is then formed from the PI precursor to form a PI wet gel. This wet gel is dried to produce a PI dry gel (aerogel). In the third method, a PI precursor is synthesized and then a PI precursor solution or a swollen mass is prepared. An imide is then formed from the PI precursor and simultaneously gelled to produce a PI wet gel. In the third method, a PI precursor is synthesized and then a PI precursor solution or a swollen mass is prepared. The solution / swollen mass is gelled to produce a PI precursor wet gel. The wet gel is then dried to produce a PI precursor xerogel. Imide is then formed from the PI precursor xerogel to form a PI xerogel (aerogel).

[0313] As a further example, Leventis et al. [Polyimide Aerogels by Ring-Opening Metathesis Polymerization (ROMP), Chem. Mater. 2011, 23, 8, 2250-2261] discusses the formation of PI aerogels using the ROMP method. A low molecular weight imidized oligomer terminated with a polymerizable group is provided and mixed with a polymerization (e.g. ROMP) catalyst. Polymerization is then initiated to produce a cross-linked polyimide. This polyimide is gelled and dried to form a PI aerogel. Leventis et al. [U.S. Pat. No. 9,745,198; Chidambareswarapattar et al, One-step room-temperature synthesis of fibrous polyimide aerogels from anhydrides and isocyanates and conversion to isomorphic carbons, J. Mater. Chem., 2010, 20, 9666-9678] also teach the formation of PI aerogels by mixing a dianhydride (e.g., PMDA) with an isocyanate (e.g., 4,4'-diisocyanatodiphenylmethane or methylene di-p-phenylene diisocyanate) to form a sol-gel material. The sol-gel material is then dried to produce a PI aerogel. Leventis et al. [Isocyanate-Derived Organic Aerogels: Polyureas, Polyimides, Polyamides, MRS Proceedings, 1306 (2011), Mrsf10-1306-bb03-01.doi: 10.1557 / opl.2011.90] also noted that DESMODUR N3300A, DESMODUR RE and MONDUR CD (all from BAYER CORP.) can also be used as isocyanates.

[0314] In an alternative approach, Guo et al. [Polyimide Aerogels Cross-Linked through Amine Functionalized Polyoligomeric Silsesquioxane, ACS Appl. Mater. Interfaces 2011, 3, 546-552] discusses the formation of PI aerogels by reacting aminosilsesquioxane with polyamic acid oligomers terminated with anhydride groups. The product is imidized (although thermal imidization is also considered) and gelled using pyridine, and then dried to obtain PI aerogels. Nguyen et al. [Development of High Temperature, Flexible Polyimide Aerogels, American Chemical Society, a collection of papers published in 2011] discusses the preparation of branched polyimides by mixing diamines and dianhydrides and imidizing, followed by reaction with polyamino compounds (e.g., 1,3,5-tris(4-aminophenoxybenzene)). The product is then reacted with 4,4'-methylene diisocyanate and dried to form PI-urea aerogels.

[0315] In other embodiments, Meador et al. [Mechanically Strong, Flexible Polyimide Aerogels Cross-Linked with Aromatic Triamine, ACS Appl. Mater. Interfaces, 2012, 4 (2), pp 536-544] discusses the production of PI gels by crosslinking polyamic acid oligomers terminated with anhydride groups in solution with aromatic triamines and then imidizing. The resulting wet material is dried to form PI aerogels. In addition, Meador et al. [Polyimide Aerogels with Amide Cross-Links: A Low Cost Alternative for Mechanically Strong Polymer Aerogels, ACS Appl. Mater. Interfaces 2015, 7, 1240-1249] discusses the formation of PI gels by crosslinking amine-terminated oligomers with 1,3,5-benzenetricarbonyl trichloride. The resulting gel is dried to form a PI aerogel.

[0316] In another embodiment, Pei et al. [Preparation and Characterization of Highly Cross-Linked Polyimide Aerogels Based on Polyimide Containing Trimethoxysilane Side Groups, Langmuir 2014, 30, 13375-13383] produced PI aerogels from polyimide containing trimethoxysilane side groups, which is a condensation product of polyimide containing acyl chloride side groups and 3-aminopropyltrimethoxysilane. The resulting gel is dried to form a PI aerogel.

[0317] In any of these methods, a graphene suspension can be added (see Zhang et al, Graphene / carbon aerogels derived from graphene crosslinked polyimide as electrode materials for supercapacitors, RSC Adv., 2015, 5, 1301).

[0318] Each of these methods can produce a polyimide aerogel, and the present invention contemplates any suitable method for producing such a polyimide aerogel. According to certain embodiments of the present invention, regardless of which method is used to produce the PI aerogel, the resulting PI aerogel can be pyrolyzed to form a PI-derived carbon aerogel. According to certain embodiments discussed herein, additives such as silicon can also be introduced.

[0319] All cited publications are incorporated herein by reference in their entirety. Additionally, if a definition or use of a term in a reference incorporated herein by reference is inconsistent or contrary to the definition of that term provided herein, the definition of that term provided herein applies and the definition of that term in the reference should be disregarded.

[0320] The above advantages as well as those apparent from the foregoing description are effectively obtained.Since certain changes could be made in the above construction without departing from the scope of the invention, it is intended that all matter contained in the above description or shown in the accompanying drawings shall be interpreted as illustrative and not limiting.

[0321] It is also to be understood that the appended claims are intended to cover all generic and specific features of the invention described herein and all statements of the scope of the invention which, as a matter of language, might be said to fall therebetween.

Claims

1. A carbon composition comprising: A carbon aerogel having a pore structure comprising a fibrous morphology, the pore structure comprising an average pillar width of 2 to 10 nm, and a silicon-based material, said silicon-based material being present at least partially within the pore structure of said carbon aerogel, The carbon aerogel includes more than 10 wt % of the silicon-based material, the porosity of the carbon composition is 50% to 80%, the pore size at the maximum peak from the distribution is 100 nm or less, and the silicon utilization is at least 20%, and the carbon aerogel has a Young's modulus of at least 0.2 GPa and a density of 0.15 g / cc to 1.5 g / cc according to ASTM E2546 or ISO 14577, wherein the silicon utilization is calculated by the following formula: , The theoretical capacity per gram of silicon is 4200 mAh / g.

2. The carbon composition of claim 1, wherein the carbon aerogel has an electrical conductivity of at least 10 S / cm.

3. The carbon composition of claim 1, wherein the carbon aerogel comprises a polyimide-derived carbon aerogel.

4. The carbon composition of claim 1 or 2, wherein the carbon aerogel comprises at least 4 wt% residual nitrogen.

5. The carbon composition according to claim 1 or 2, wherein the carbon aerogel is in a monolithic form.

6. The carbon composition according to claim 5, wherein the monolithic carbon aerogel is free of a binder. 7 . The carbon composition according to claim 6 , wherein the monolithic carbon aerogel has a thickness of 10 to 500 microns.

8. The carbon composition according to claim 1 or 2, wherein the carbon composition is in the form of particles.

9. The carbon composition of claim 8, wherein the particulate carbon composition has a diameter of 1 micron to 50 microns.

10. The carbon composition of claim 1 or 2, wherein the carbon aerogel comprises 25% to 65% silicon by weight of the carbon aerogel.

11. The carbon composition of claim 1 or 2, wherein the carbon composition has a capacity of at least 800 mAh / g.

12. An electrode comprising the carbon composition according to claim 1 or 2.

13. An energy storage device comprising the carbon composition according to claim 1 or 2.

14. The energy storage device of claim 13, wherein the energy storage device is a lithium-ion battery.

15. A method of forming a carbon composition comprising a carbon aerogel, the method comprising: Providing a mixture of a polyimide precursor and a silicon-based material, imidizing the mixture chemically or thermally; drying the imidized mixture to produce a porous polyimide-silicon composite; as well as carbonizing the porous polyimide silicon composite material to produce the carbon composition, the carbon composition having greater than 10 wt% silicon, and a porosity of 50% to 80%, and a pore size at a maximum peak from a distribution of 100 nm or less, the carbon aerogel having a pore structure including a fibrous morphology, wherein the silicon-based material is at least partially present within the pore structure of the carbon aerogel, and The carbon aerogel has a Young's modulus of 0.2 GPa to 8 GPa and a density of 0.15 g / cc to 1.5 g / cc according to ASTM E2546 or ISO 14577. The method according to claim 15 , wherein the carbon composition is formed into a monolith.

17. The method of claim 15, further comprising combining the mixture with a medium immiscible with the mixture, thereby forming droplets of the imidized mixture.

18. The method of claim 17, further comprising drying the droplets to form particles.

19. The method of claim 18, wherein the particles have a diameter of 1 micron to 50 microns.

20. The method of claim 15, wherein the maximum pyrolysis temperature is 750°C to 1600°C.

21. The method of any one of claims 15 to 20, wherein the carbon composition has a capacity of at least 800 mAh / g.

22. The method of any one of claims 15 to 20, wherein the carbon composition has a silicon utilization of at least 20%, wherein the silicon utilization is calculated by the following formula: , The theoretical capacity per gram of silicon is 4200 mAh / g.

Citation Information

Patent Citations

  • Carbon aerogel-based electrode materials and methods of manufacture thereof

    US11648521B2

  • Methods for manufacture of aerogels

    US20060084707A1

  • Process for forming transparent aerogel insulating arrays

    US4610863A

  • Method for producing metal oxide aerogels having densities less than 0.02 g / cc

    US5275796A

  • Method for making monolithic metal oxide aerogels

    US5395805A